Effect of Notoginsenoside R1 on reparative dentin formation via regulating the function of human dental pulp stem cells - Xuan He; Dan Liang; Xinyi Zhao; Kaixin Liu; Zicheng Zhang; Meiling Li; Xuemeng Ma; Wenxia Chen; Xiaoyi Zhong (Tissue and Cell, 2027)

Integrative multi-omics analysis reveals genetic and epigenetic regulatory networks of body weight in the mud crab (Scylla paramamosain) - Qionghui Qin; Weiren Zhang; Meiling Liang; Yijia Shih; Yaodong Zhang; Siyi Zhou; Kewei Huang; Xiaopeng Wang; Haihui Ye (Aquaculture, 2027)

Multi-omics Mendelian randomization and machine learning identify candidate therapeutic targets for Alzheimer’s and Parkinson’s diseases - Xun Li; Lei Zhang; Jinyan Xia; Meiling Zheng; Zhipeng Zhou; Jing Cai (Mammalian Genome, 2026)

Liensinine can improve vascular remodeling in hypertension through the ferroptosis-related TLR4 inflammatory pathway - Daxin Chen; Peizhi Jia; Meiling Wang; Baojie Du; Haitao Du; Xi Huang; Jianwei Zeng; Qiaoyan Cai; Ling Zhang; Ying Zhu; Shan Lin; Dawei Lian; et al. (Journal of Molecular Medicine, 2026)

Exogenous dissolved organic matter redirects humic carbon fate at mineral interfaces through pre-contact molecular conditioning - Yu Li; Guangxu Mi; Jianghao Cheng; Meiling Zhang; Ying Liu; Shuang Ai; Fan Yang; Kui Cheng (Water Research, 2026)

Research on design and applications of multistable mechanical metamaterial structures with high fatigue resistance - Song Gao; Meiling Zhang; Lang Yu; Jinkui Chu; Jianwei Sun; Luquan Ren (Engineering Structures, 2026)

Bending behaviour of cementitious composite beams reinforced with 3D-printed TPMS geometries - Vuong Nguyen-Van; S. Sankeeth; Nabodyuti Das; Bao-Loi Dang; Y.X. Zhang; Meiling Dai (Engineering Structures, 2026)

Nonlinear buckling responses of a confined liner reinforced by functionally graded graphene with atom vacancy defects under thermal-mechanical loading - Qian Zhang; Shiyi Zhang; Meiling Shen; Zhaochao Li (Engineering Structures, 2026)

A natural special-shaped MXene/bamboo evaporator with synergistic hydrothermal management for solar water purification - Jinhong He; Zongpei Zhang; Tianqing Shu; Weisheng Yang; Xiaoxu Ma; Jingren Ma; Meiling Chen; Fengshan Zhang; Guigan Fang; Huining Xiao; Jingquan Han (Desalination, 2026)

Comparative Lipidomics and microstructural characterization of Milk fat globule membrane protein powders from bovine buttermilk and cheese whey - Kuolin Si; Mengxueyao Zhang; Xuexing Zong; Yin Pei; Lu Liu; Xiuxiu Zhang; Meiling Ge; Xiaodong Li; Qingquan Yan (Food Research International, 2026)

Zeolitic imidazolate framework enabled heat-resistant enzymatic biosensor for real-time and non-invasive detection of glucose - Qingwen Zhang; Meiling Yuan; Jingwen Chen; Ying Yang; Meng Lu; Chaoyue Cui; Xiaohu Liu; Hu Chen; Yi Wang (Chemical Engineering Journal, 2026)

Chemical reaction driven interfacial reconstruction of In2O3/S-BiOCl heterojunction with Ag2S quantum dots enables a self-validated fluorescence/photoelectrochemical dual mode nitrite sensing - Jingshu Li; Yuee Zhong; Manqi Li; Jiawei Zhou; Hengwen Tang; Jing Liu; Jianru Tang; Xiaohua Zhu; Youyu Zhang; Meiling Liu (Analytica Chimica Acta, 2026)

A double-platform assay for rapid and on-site detection of chikungunya virus by integrating catalytic hairpin assembly with lateral flow immunochromatography assay - Ruijie Lu; Dawen Chen; Ai Chen; Shuo Ma; Yuming Yao; Yaya Chen; Gulinaizhaer Abudushalamu; Meiling Zhou; Xiao Li; Yue Zheng; Wenjing Lu; Yueqi Wang; et al. (Analytica Chimica Acta, 2026)

Rapid Detection of Spring Viremia of Carp Virus ( SVCV ) Using RAA ‐ CRISPR /Cas12a - Xiaoyang Li; Aoqing Zhang; Yingying Li; Yingying Wang; Hao Zheng; Defeng Zhang; Yan Ren; Xubing Mo; Yuting Deng; Junyu Luo; Meiling Yu; Bo Chen; et al. (Journal of Fish Diseases, 2026)
Spring viremia of carp virus (SVCV), that can infect cyprinoid and koi causing an acute hemorrhagic symptom, with a feature of widespread epidemic, which poses a severe threat to the global aquaculture industry. Given the absence of specific effective medicine or vaccines, the early, accurate diagnosis is critical in the disease prevention. Many SVCV detection methods have been established, but most require specialized equipment and skilled operators, which limits their field application. In this study, we established a recombinase‐mediated isothermal amplification (RAA) in conjunction with the CRISPR/Cas12a system targeting the screened conserved region of the G gene in the genome to identify SVCV. The optimal combination of the primer pairs and crRNA was screened via the fluorescence intensity. In addition, the test exhibited high sensitivity and specificity, which could detect at the limit of 1.243 × 10 1 copies/μL and show no cross‐reactivity with other common freshwater fish pathogens. Furthermore, the result could be visible by excitation of fluorophores by blue light at 39°C within 30 min. The integrated method combines the advantages of RAA and CRISPR‐based signal transduction, offering a diagnosis project in resource‐limited aquaculture environments and a field‐applicable early warning of SVCV.

Mapping mollic epipedon thickness via ground-penetrating radar based on the combined method of Variational Mode Decomposition and Average Envelope Amplitude - Haipeng Lu; Xiangming Zhu; Wenjuan Zheng; Bin Zhang; Tianhao Wang; Yu Zhang; Meiling Fu; Enhua Ran (Soil and Tillage Research, 2026)

Artificial humic acid reshapes microbial C-N metabolism and nitrogen partition in microplastic-contaminated soils - Qihe Gao; Shuang Ai; Meiling Zhang; Yu Li; Yantong Li; Yadong Ma; Jiale Zhang; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2026)

Twisted aromatic backbone engineering enables high-performance anion exchange membranes for durable water electrolysis - Wenjing Li; Jinsheng Li; Pingxia Zhang; Wei Qi; Xue Wang; Feiyan An; Youze Zeng; Dong Pan; Rina Sa; Meiling Xiao; Wei Xing; Jianbing Zhu; et al. (Chemical Engineering Journal, 2026)

Inner Ear Organoids: Recent Progress and Challenges - Yingxinyu Li; Cairong He; Jiayan Liu; Haiqin Zhang; Hongxia Zhang; Zheyu He; Mengyang He; Meiling Chen; Feiyan Zhou; Jie Ding (Stem Cell Reviews and Reports, 2026)

Mild hydrolysis and upgrading utilization of waste PET: Preparation of regenerated TPA and MOF materials and study of their adsorption performance - Wei Lin; Meiling Zhang; Shun Zhang; Sheng Shi; Zeyu Wang; Chengyong Gao; Shuhua Wang; Enbin Zhu (Sustainable Chemistry and Pharmacy, 2026)

Sophoraflavanone G disrupts human sperm function via impairing CatSper-mediated Ca2+ signaling - Meiling Yang; Ze Xu; Jiali Zhang; Nanxi Ji; Jieling Huang; Yiling Lu; Chunli Sha; Sijie Gaoliu; Xuhui Zeng; Hang Kang; Liping Chen (Reproductive Toxicology, 2026)

Uncovering the synergistic effects of digital–intelligent transformation and industrial structure upgrading on eco-efficiency:Evidence from 284 Chinese cities - Meiling Wu; Wei Liu; Rongguang Zhang; Yuying Yue (Journal of Cleaner Production, 2026)

An NSGA-III–based predict–optimize–evaluate framework for low carbon land use optimization: A case study of the Yangtze River Delta - Menglin Yu; Jie Tao; Peng Zhang; Meiling Zhou; Beiying Huang; Jie Guo; Jialin Yi (Journal of Environmental Management, 2026)

Impact of Fly Ash on the CO2 Mineralization Efficiency and Interfacial Transition Zone Properties of Sustainable Coal Gangue-based Materials - Lei Qin; Feilong Zhang; Zitong Xue; Hui Wang; Miao Mu; Meiling Xiong; Niandong Chen (Water, Air, & Soil Pollution, 2026)

TRPV4/IP3R-1-mediated endothelial pyroptosis drives pulmonary microvascular endothelial permeability in endotoxin-induced acute lung injury - Shasha Liu; Shuan Dong; Lirong Gong; Jing Yang; Huayang Liu; Meiling Piao; Ya Wu; Huirong An; Li Zhang; Jianbo Yu (Inflammation Research, 2026)

Spatiotemporal cube for identifying Cd-dominated heavy metal stress in rice using signal decomposition and hotspot analysis from GF-6 time series images - Yanan Wen; Tianyi Wang; Meiling Liu; Hui Zhang; Yuxin Zhao; Ben Yang; Xutao Yan; Ling Wu (International Journal of Remote Sensing, 2026)

Experimental study on the bearing performance of high pile cap foundation under the coupling effect of scouring and horizontal cyclic loads - Lunliang Duan; Linghao Zhang; Pei Yuan; Yankun Zhang; Duoyin Wang; Meiling Fan; Bo Geng (Soil Dynamics and Earthquake Engineering, 2026)

Linking molecular heterogeneity of artificial humic acid to divergent cadmium coordination behaviors - Yu Li; Xianghui Meng; Shuang Ai; Meiling Zhang; Guangxu Mi; Yurun Miao; Zhuqing Liu; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2026)

Organophosphate flame retardants and immunotoxicity: An integrated bibliometric and systematic review of epidemiological and mechanistic evidence - Chengyue Ma; Yuhao Zhong; Xiaowen Huang; Minghui Li; Jinsong Zhao; Chunji Wang; Fang Zhang; Yue Jia; Yuxin Jiang; Yingli Li; Meiling Shi; Shuqi Chen; et al. (Journal of Environmental Sciences, 2026)

Synergistic atomic-level anchoring and pore engineering of cobalt-nitrogen-carbon for anti-fouling and robust capacitive deionization - Huakun Pan; Haodong Zhang; Xinxi Teng; Yang Fan; Yaming Wang; Lin Li; Guisong Zhang; Meiling Liu; Haiou Song; Aimin Li; Shupeng Zhang (Chemical Engineering Journal, 2026)

Genome-wide analysis of the papaya bZIP gene family identifies CpbZIP52 as a key regulator of fruit postharvest ripening - Meiling Ding; Shanni Cao; Meng Zeng; Min Zhang; Hongya Tang; Xiaochun Chen; Xianqi Fu; Sicheng Bai; Min Yang; Kaidong Liu (Plant Science, 2026)

Buckling of the constrained subsea FGP-GPLs liner under pressure loading and heating field based on multi-source data fusion scheme - Qian Zhang; Shiyi Zhang; Meiling Shen; Zhaochao Li (Ocean Engineering, 2026)

Synergy of interfacial modification and sustained release in plant-derived nanoliposomes for enhanced pesticide efficacy and dose reduction - Zhongxiang Zhao; Xipeng Jiang; Meiling Yang; Juan Yang; Shujie Ma; Lili Dong; Fengyue Suo; Jingao Dong; Lihui Zhang (Journal of Environmental Chemical Engineering, 2026)

Dissolved organic matter dynamics and antibiotic resistance gene attenuation during composting: Characteristics and interrelationships - Dongfang Shi; Meiling Shi; Shengnan Zhang; Pengyan Zhang; Xiaoyan Qian; Yongjun You; Chong Liu; Fayong Li (Journal of Environmental Chemical Engineering, 2026)

Study on the removal effect of Enteromorpha polysaccharide on heavy metal-organic composite pollution - Xue Shen; Yingqiang Li; Meiling Li; Yaru Zai; Xue Han; Shida Zhang; Jin Wang; Zhigang Yang; Yang Song (Journal of Environmental Chemical Engineering, 2026)

Zwitterionic polyurethane-based solid polymer electrolytes for high-performance solid-state Lithium metal batteries - Jiaxing Liu; Bei Deng; Meiling Liu; Yaxue Zhang; Zhihao Yang; Tieqi Huang; Hongtao Liu (Chemical Engineering Journal, 2026)

Co-exposure to PS-NPs and HFPO-TA potentiates reproductive toxicity via ferroptosis and SLC1A5-Mediated glutamine deprivation in male mice - Lihai Wu; Jing Ding; Jiayu Xue; Meiling Le; Yiqi Wan; Wanting Zhao; Yangyang Yuan; Xiaodong Kuang; Xinyuan zhao; Liping Zheng; Dalei Zhang (Chemico-Biological Interactions, 2026)

A photothermal conversion phase change composite material with energy storage and long-term heat release based on banana nanocellulose/montmorillonite aerogel - Meiling Zhang; Hui Wen; Jianhao Shao; Xupin Zhuang; Zhangang Wang (Biomass and Bioenergy, 2026)

Design and Performance Evaluation of Amino Acid-Decorated UiO-66-NH2/Pebax Mixed Matrix Membranes for Efficient CO2 Separation - Xiaochun Jing; Wei Zhao; Pengzhi Bei; Hongjing Liu; Yan Dai; Xu Zhao; Chengpeng Zhang; Meiling Shi; Ying Zhang (Water, Air, & Soil Pollution, 2026)

Aneuploid gametes produced by triploid Populus ‘Beilinxiongzhu 1#’ transmit higher paternal heterozygosity to progeny - Yaru Sang; Yunyun Xie; Yifan Zhao; Bo Kong; Dawei Cheng; Liang Li; Lexun Ma; Jiahua Du; Meiling Long; Dongliang Cao; Zhang Huajian; Lao Huiqi; et al. (Tree Genetics & Genomes, 2026)

Construction of a plasmid-based reverse genetics system for the rescue of shrimp infectious covert mortality nodavirus (CMNV) and use in deciphering the role of its B2 protein in regulating its cross-species infectivity - Zhenxin Zhao; Ting Xue; Jinwu Wang; Rui Xiao; Yue Zhang; Meiling Sun; Qingli Zhang; Huarong Guo (Aquaculture, 2026)

Recycling and valorization of waste colored polyester through a zero-waste approach - Yazhou Wang; Shuhua Wang; Ji Lan; Shaoping Jiang; Yufang Weng; Sheng Shi; Chengyong Gao; Meiling Zhang (Waste Management, 2026)

Extracellular polymeric substances mediated mechanisms underlying acyl homoserine lactones regulated biofilm formation in Pseudomonas aeruginosa - Cunxin Guo; Meiling Tong; Jianlin Kang; Yao Zhu; Aiyu Zhang; Jinsong Guo; Fang Fang (Journal of Water Process Engineering, 2026)

Multifunctional metallized basalt/PA6 composites: EMI shielding, joule heating, and tunable rigidity - Jiajun Du; Hao Shi; Xin Wang; Meiling Xiang; Jing Zhang (Chemical Engineering Journal, 2026)

Interleukin-12 Supports Self-renewal Division of Mouse Hematopoietic Stem Cells in Polyvinyl Alcohol-Based Culture - Jinglei Zhai; Xialin Li; Meiling Yin; Sen Zhang; Xiaoming Liu; Lisha Wang; Nini Wang; Lin Wang; Hideo Ema; Fang Dong (Stem Cell Reviews and Reports, 2026)

Effects of different dark septate endophyte species on growth, Pb tolerance and associated physiological responses in Astragalus membranaceus under Pb stress - Gen Li; Meiling Wu; Qingqing Liu; Yashuo Tian; Simiao Wang; Yibang Zhang; Qing Dang; Fei Cao; Li Han (Plant and Soil, 2026)

Association of metabolic status and genetic predisposition with healthy ageing and life expectancy across obesity levels: a prospective cohort study in the context of 3P medical approaches - Cancan Li; Haotian Wang; Huimin Lu; Meiling Cao; Jie Zhang; Shengzhi Sun; Youxin Wang (EPMA Journal, 2026)

Exogenous plant growth-promoting rhizobacteria boosting photosynthetic efficiency via thylakoid lipid restructuring in potato under low-potassium conditions - Xin Zhou; Xin Cheng; Baoyu Fu; Meiling Li; Chao Luo; Haoyang Gong; Hongkun Yang; Jingye Fu; Chengcheng Cai; Kaiqin Zhang; Shunlin Zheng (Plant Science, 2026)

Shifting patterns in tropical lake phytoplankton communities coinciding with anthropogenic nutrient and pollutant trends - Dongna Yan; Yongming Han; Patrick Rioual; Jianghu Lan; Sifan Zan; Yalan Tang; Huijia Zhang; Meiling Guo; Eric Capo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Singlet oxygen-dominated dual-pathways catalytic ozonation of sulfamethoxazole over FeOx-N-BC/O3–MNBs system - Meiling Cai; Xiaojun Miao; Xiaoyan Wang; Xueyan Xue; Hui Zhu; Liping Yang; Xinqian Zhang; Jiao Yin (Journal of Environmental Chemical Engineering, 2026)

Bridging data gaps in landslide early warning: Physics-derived rainfall thresholds under rainfall uncertainty - Hao Zou; Weiye Huang; Ting Liu; Henghao Cai; Shuai Mao; Bing Chen; Meiling Wu; Qingyu Zhang; Xiao Liu; Shu Zhang (Engineering Geology, 2026)

Deep-sea bamboo corals: New Jasonisis species from Indian and Atlantic ridges and pan-oceanic genetic connectivity of Tridentisis candelabrum - Meiling Ge; Xinlong Li; Xin Tian; Ningxia Xu; Xuying Hu; Yu Xu; Zongling Wang; Xuelei Zhang; Qinzeng Xu (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Pioneer Plants Improved the Suitability of Lead–Zinc Tailings for Plant Growth - He Gong; Xusheng Jiang; Hui Qiu; Luyang Wang; Meiling Zhang; Xinyue Teng; Jie Liu (Water, Air, & Soil Pollution, 2026)

Impact of mid-high-latitude Eurasian ISO on extreme hot days in the middle-lower reaches of the Yangtze River valley during boreal summer - Meiling Zhang; Shuangyan Yang; Zhiwei Zhu; Tim Li (Climate Dynamics, 2026)

Coupled crack-rainfall mechanism of a retrogressive landslide: field investigation and monitoring in Southwest China - Qiuxiang Huang; Shupeng Li; Meiling Xiong; Chu Zhang; Yan Zhou (Bulletin of Engineering Geology and the Environment, 2026)

Pore Structure Characteristics and Controlling Factors of Different Lithofacies in Lacustrine Shale: A Case Study of Fengcheng Formation in Mahu Sag, Junggar Basin - Jiahao Lyu; Fujie Jiang; Jing Xue; Tao Hu; Yuping Wu; Chenxi Zhang; Meiling Hu; Renda Huang (Journal of Earth Science, 2026)

Investigation of Oil Content in Lacustrine Shale-Oil Systems: Insights from Two Different Pyrolysis - Yuping Wu; Chenglin Liu; Fujie Jiang; Tao Hu; Chenxi Zhang; Jiahao Lyu; Renda Huang; Meiling Hu; Guanyun Wu; Rizwan Sarwar Awan (Journal of Earth Science, 2026)

Study on ball milling driven solvent extraction – Ozone oxidation decolorization of waste printed polyester fabrics - Xiao Li; Chengyong Gao; Wansi Li; Sheng Shi; Enbin Zhu; Meiling Zhang; Shuhua Wang (Process Safety and Environmental Protection, 2026)

Effects of humic acid and microbial agents on contaminated manure composting: Heavy metal passivation, gaseous emission mitigation and microbial community response - Meiling Shi; Xiaojuan Wang; Jie Gu; Xuefei Hu; Fayong Li; Yongjun You; Pengyan Zhang (Process Safety and Environmental Protection, 2026)

Iron single-atom/cluster nanozyme with enhanced oxidase-like activity for fluorescent/colorimetric analysis of Total antioxidant capacity in food - Meiling Chen; Yongmin Lei; Junlin Liu; Qiming Liu; Xingjian Song; Ting He; Guo-jun Zhang; Yujie Sun; Yulin Zhang; Yuqing Qin; Shaowei Chen (Food Chemistry, 2026)

Alleviating Clostridium perfringens-Induced Gut Lesionsin Broiler Chickens by Orally Administered Bovine Intestinal Alkaline Phosphatase - Wangli Ji; Daoxin Yang; Wenjing Zhang; Yuan Wang; Zhenzhen Hao; Kairui Guo; Xianhua Sun; Shuai Wang; Shuyan Yang; Jianshuang Ma; Huiying Luo; Bin Yao; et al. (Probiotics and Antimicrobial Proteins, 2026)

Research on high-resolution PM2.5 concentration estimation methods based on transfer learning - Meiling Xing; Bo Li; Wenhao Zhang; Guohong Li; Xiufeng Yang; Qiyue Liu; Qichao Zhao (Advances in Space Research, 2026)

Porous Eu-ox metal–organic framework enabling open-channel carrier transport and durable Pb2+ immobilization in perovskite solar cells - Zhihang Zhang; Xiaolong Cao; Tiantian Lv; Zhengyan He; Haiyan Sun; Hai Zhong; Qi Zhang; Changlin Yao; Wen Li; Shufang Zhang; Meiling Feng (Chemical Engineering Journal, 2026)

Microbial-driven iron transformation and carbon stabilisation in flooded soils: roles of biochar and rock weathering - Qiao Xu; Gefeng Zhang; Feifan Zhang; Tharanga Bandara; Hongyan Guo; Meiling Xu; Caixian Tang (Plant and Soil, 2026)

Evaluation of the antibacterial and antioxidant potential of the endophytic fungus EFY14 from Cannabis sativa L. leaves through metabolomics and molecular docking - ShanShan Li; MeiLing Zhang; Ying Zhai; Yan Zhao; Ming Zhao; LiJie Liu; FeiYao Zhong; ZhiGang Wang; Shuai Li (Natural Product Research, 2026)

Comparative assessment of female reproductive toxicity from PFOA and its alternative GenX in mice and human granulosa cells - Yangyang Yuan; Binhui Wang; Yuyu Fan; Meiling Le; Lihai Wu; Shiyi Deng; Jian Huang; Dalei Zhang (Toxicology and Applied Pharmacology, 2026)

Seasonal gut microbiota and functional dynamics in brittle star (Ophiothrix exigua) from the Yellow Sea, China - Md. Tariful Islam Fuad; Yue Dong; Zhong Li; Meiling Ge; S.M. Sharifuzzaman; Xiaoshou Liu; Xuelei Zhang; Qinzeng Xu (Marine Environmental Research, 2026)

Cationic polyacrylamide (CPAM) assisted leaching of rare earth ore containing clay minerals by inhibiting swelling and promoting permeation of ammonium sulfate solution - Meiling Jiang; Huifang Yang; Wenqian Cui; Yunbo Yang; Zhenyue Zhang; Zhengyan He; Zhigao Xu; Ming Wu; Jun Zhao; Ruan Chi (Hydrometallurgy, 2026)

Characterization of a myoinhibitory peptide and its role in neuroimmune regulation in Litopenaeus vannamei during Vibrio harveyi infection - Yongxiong Huang; Meiling Huang; XuYan Tan; Zhiqiang Zhang; Jia Cai; Yishan Lu; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2026)

Spatiotemporal graph for detecting evolution characteristics of karst rocky desertification from long time-series Landsat images - Yanan Wen; Meiling Liu; Zeyan Wu; Qian Zhang; Jialei Su; Zijian Hu (CATENA, 2026)

Effectiveness and mechanism of in situ sludge biochar carrier enhancing salt-tolerant bacteria for pyrazolone degradation in high-salinity pharmaceutical wastewater - Yuying Ma; Zheyu Chen; Genping Yi; Ezzat H Elshazly; Qingshan Liu; Hongyan Zhang; Meiling Zheng; Aijie Wang; Wenzong Liu (Bioresource Technology, 2026)

Optimal information transmission in a non-Markovian auto-regulatory gene expression system - Zihao Wang; Meiling Chen; Zhenquan Zhang; Xiyan Yang; Tianshou Zhou; Changhong Shi; Jiajun Zhang (BioSystems, 2026)

Reciprocal rate-modulated evolution of slow-moving reservoir landslide: learning from hydrological-adapted block model - Shu Zhang; Qiang Li; Huiming Tang; Zongxing Zou; Jianfan Zhao; Jiefei Zhang; Meiling Wu (Landslides, 2026)

Bio-inspired fabrication of heterostructured porous core-shell PANI@Cu2O/CMC composite beads for green catalysis in A3 and decarboxylative A3 couplings - Shuyao Zhang; Ting Lin; Yuling Huang; Jiayi Huang; Meiling Xue; Zhihao Shan; Yiqun Li (Sustainable Chemistry and Pharmacy, 2025)

Spatial accessibility to public electric vehicle charging infrastructure and multi-mechanism process of regional inequity in Greater Bay Area, China - Xing Gao; Huizi Wang; Ying Zhang; Keyu Zhai; Meiling Wu (Journal of Transport Geography, 2025)

Long non-coding RNA profiling reveals lncRNA MslncLOX13S that promotes lipoxygenase gene expression and enhances the tolerance to selenium in Medicago sativa L. - Qingdong Wang; Mengli Xu; Meiling Xiang; Yarui Sheng; Huafeng Hu; Tianyu Zhang (Journal of Plant Physiology, 2025)

Effects of long-term plastic film mulching on microplastic and phthalate esters pollution in salt-affected soils: Microbial community shifts and enrichment of putative degraders - Jiabin Li; Yunfeng Pu; Yongjun You; Shengnan Zhang; Xiaoyan Qian; Meiling Shi; Guocai Ma; Chong Liu; Kamel M. Eltohamy; Fayong Li (Journal of Hazardous Materials, 2025)

Structure design and future development of lithium ion sieve bulk adsorbents - Rongye Zhang; Chenyang Li; Meiling Wang (Journal of Environmental Chemical Engineering, 2025)

Changes in soil quality and crop productivity along rice cultivation chronosequences in saline-alkali soils - Bangyan Zhang; Jinmin Wu; Xiaolong Bai; Lei Li; Meiling Lin; Xing Xu; Fengju Zhang; Bin Wang (Journal of Environmental Management, 2025)

FeOOH@HAnB catalyst with exposed (211) facet: High stability and new degradation routes for tetracycline - Yingru Huang; Meiling Zhou; Yaping Zhang; Yufeng He; Yuanyuan Xie; Rongmin Wang (Environmental Research, 2025)

Visible light driven highly selective oxidation of HMF coupled with H2 evolution via bimetal-doped synergism on ZnIn2S4 nanosheets - Yachen Hu; Wei Jiang; Zijun Zhang; Qinqin Jiang; Yawen Jiang; Lang Sun; Panjing Xu; Yanling Chang; Chuanqiang Wu; Ziming Fan; Meiling Wang; Zhou Chen; et al. (Chemical Engineering Journal, 2025)

The role of the casein kinase 1 (CK1) family in fungal infections - Meiling Wu; Haolin Zhang; Miao Jia; Xingyu Cao; Juan Wang (Molecular Biology Reports, 2025)

Integrating network pharmacology, molecular docking, and bioinformatics to explore the mechanism of sparganii rhizoma in the treatment of laryngeal cancer - Meiling Zheng; Rui Zhang; Xinxing Yang; Feiyan Wang; Xiaodi Guo; Long Li; Jin Wang; Yajun Shi; Shan Miao; Wei Quan; Shanbo Ma; Xiaopeng Shi (Molecular Diversity, 2025)

Climate and soil nutrients jointly affect the variations in microbial nutrient limitation with elevation in sedge peatlands - Tao Zhang; Yimeng Wang; Ming Wang; Shengzhong Wang; Guodong Wang; Meiling Zhao; Jingci Meng; Yusong Yuan; Nanlin Hu (Applied Soil Ecology, 2025)

Long-term nitrogen enrichment affects soil organic carbon fractions through microbial pathways in fluvo-aquic soil - Binggeng YANG; Jiwen CUI; Meiling ZHANG; Kangrui FANG; Chao AI; Tengfei GUO; Shaomin HUANG; Dali SONG; Wei ZHOU (Pedosphere, 2025)

Nanoplastics in infusion system remains underexplored: Evidence from detected nanoplastics in hospital-sourced infusion products - Licheng Wang; Jing Peng; William Ji; Muhammad Ali Tahir; Jilun Wang; Tao Wang; Meiling Weng; Liwu Zhang (Journal of Hazardous Materials, 2025)

Possible influences of tropical vegetation shift on the glacial-interglacial temperature changes - Liping Tian; Cong Chen; Mengyuan Wang; Chuanxiu Luo; Xiao Zhang; Yanming Ruan; Jiantao Cao; Meiling Man; Zhuo Zheng; Xiaoqiang Yang; Kangyou Huang; Li Li; et al. (Global and Planetary Change, 2025)

Alternating current charging-strengthened anode interface and cathode prelithiation synergistically improve comprehensive performances of LiFePO4||graphite batteries - Meiling Wu; Yulong Zhang; Shiyou Li; Lei Niu; Ningshuang Zhang; Xiaoling Cui (Chemical Engineering Journal, 2025)

Efficient removal of antibiotics and synthetic dyes using VTMS-functionalized N/S-GQDs-PVA/cellulose composite aerogels - Muhammad Yousif; Meiling Zhang; Bilqees Hussain; Xupin Zhuang; Zhangang Wang; Hongxia Wang; Tong Lin (Chemical Engineering Journal, 2025)

Fast prediction of indoor temperature distribution under spatiotemporal variation of solar radiation using equivalent surface heat sources and multimodal CNN - Ye Yuan; Junxi Gao; Meiling Li; Gang Liu; Yuebo Yu; Zixuan Yu; Hanyuan Zhang (Building and Environment, 2025)

Sequential temperature design in high-speed railway stations: A dynamic thermal strategy balancing thermal comfort and energy efficiency - Ye Yuan; Meiling Li; Junxi Gao; Gang Liu; Zongwu Xu; Ying Chen; Hanyuan Zhang (Building and Environment, 2025)

Impacts of turbulent intermittency and pressure oscillation on persistent heavy haze pollution - Qianhui Li; Wei Wei; Hongsheng Zhang; Meiling Sun; Bingui Wu; Jingle Liu (Atmospheric Research, 2025)

2,2',4,4'-tetrabromodiphenyl ether (BDE-47) induces early hearing loss in guinea pigs via activating AhR to trigger mitochondrial and endoplasmic reticulum stress-regulated autophagy - Jie Tang; Li Zhang; Yujia Yang; Chunji Wang; Fang Zhang; Muxin Yu; Nenghua Zhang; Guangtao Xu; Bo Hu; Meiling Shi; Long Xu (Archives of Toxicology, 2025)

Wheat yield prediction using an enhanced WOFOST with soil stratified hydrothermal module driven by GLASS and ERA5-land products over Yellow River Basin - Jing Zhang; Guijun Yang; Meiling Gao; Lijie Zhang; Weinan Chen; Miao Liu; Youming Zhang; Aohua Tang; Zhenhong Li (Computers and Electronics in Agriculture, 2025)

Computed method for the thermal buckling performance of a constrained non-circular heated pipeline with an oval inverted arch - Qian Zhang; Shiyi Zhang; Meiling Shen; Zhaochao Li (Tunnelling and Underground Space Technology, 2025)

Graft−growth of Cobalt−based Prussian blue analogs on bamboo for indoor formaldehyde removal - Yi Zhu; Honghui Yan; Ruiqi Xin; Yuding Zhu; Miaomiao Zheng; Xiangxing Wu; Yiting Zhang; Ting Wang; Meiling Chen; Song Li; Jeonghun Kim; Wenkai Zhu (Environmental Research, 2025)

Diverse paths of green building development from a stakeholder collaboration perspective - Dongming Gu; Xiaofei Hu; Jianing Zhang; Meiling Chen (Energy and Buildings, 2025)

Hierarchically superhydrophobic ceramic fiber membrane with thermal-induced pore modulation for antifouling oil-water separation - Jing Jing; Zhanjian Liu; Yuxin Fu; Haonan Liu; Xiguang Zhang; Meiling Li; Huaiyuan Wang (Chemical Engineering Journal, 2025)

The intergrowth of YTa7O19 in L-Ta2O5 with Er3+/Yb3+ enhancing pure green upconversion luminescence intensity by molten salt synthesis - Yuhan Fan; Yongze Cao; Zhihua Zhang; Hualong Tao; Meiling Li; Xizhen Zhang; Sai Xu; Baojiu Chen (Chemical Engineering Journal, 2025)

CBT-Cys click ligation coupled with pregnancy test strips for nucleic acid assay - Meiling Zhang; Jiahang Song; Huawen Zhang; Yang Li; Xu Hun (Analytica Chimica Acta, 2025)

Different impacts of temperature and precipitation on vegetation net primary production of global marsh wetlands - Jiaqi Zhang; Meiling Zhao; Rong Ma; Mingming Feng; Chen Ding; Liyuan Wu; Xianguo Lu; Xiangjin Shen; Ming Jiang (Global and Planetary Change, 2025)

Tamoxifen regulates ferroptosis of hepatocytes by targeting SLC1A5 to activate hepatic stellate cells and liver fibrosis - Sha Shi; Meiling Zhang; Chengkai Zhu; Shanhao Zhu; Jie Yu; Qi Sui; Jiaqi Xu; Juan Ren; Jingnan Zhang; Peng Chen; Yi Zhang (Chemico-Biological Interactions, 2025)

Comparison of Meltpro Myco Assay with MALDI-TOF Mass Spectrometry for rapid and accurate detection of clinical Mycobacterium Species - Kehao Peng; Liuyue Xu; Xuezhi Wang; Jianming Hong; Gengchen Zhang; Yuchuan Zhao; Yinong Ye; Zengqi Huang; Jinmei Zhang; Yuchun Huang; Zhiqiao Wu; Xiaolin Yu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Different responses of cyanobacterial communities to climate change and anthropogenic activities revealed by the 500-year sedimentary record of Lake Daihai - Jing Wang; Hai Xu; Jianghu Lan; Kang’en Zhou; Yunping Song; Jin Zhang; Meiling Yang; Baoli Wang (Anthropocene, 2025)

Spatial distribution and risk assessment of microplastics in surface sediments in semi-enclosed waters: a case study of Laizhou Bay - Xuzhen Zhang; Hongxian Chu; Meiling Yin; Yadong Liu; Peng Chen; Qiangqiang Zhang; Xuejian Dai; Linghao Kong (Frontiers in Marine Science, 2025)
Marine ecosystems are the most important sinks for microplastics (MPs) from inland sources, and the input of large quantities of MPs into the oceans poses a serious threat to marine organisms and ecosystems. However, the characteristics of MPs contamination and its risk in semi-enclosed seas remain poorly understood. In this research, we conducted a comprehensive analysis and evaluation of the distribution patterns and ecological risks related to MPs found in the surface sediments of Laizhou Bay. We gathered surface sediments from various locations within the bay, which were then processed and analyzed to assess the MP content. According to the results, MPs in Laizhou Bay were widely distributed, with abundances ranging from 36–2125.5 items/g d.w. at different points, with an average of 534.7 items/g d.w. The MP forms were mainly fragments (61.91%) and particles (37.45%), with polyamide (PA) (32.73%), polyethylene terephthalate (PET) (12.42%), and polyurethane (PU) (10.81%) being the most dominant polymer types. MPs mainly originated from marine aquaculture, fishing, and domestic plastic waste; the contribution from marine activities was higher than that from land-based inputs, and their migration and dispersion were mainly affected by the hydrodynamics of water body exchange and intra-bay circulation. According to the pollution load index, the risk index of MPs in Laizhou Bay ranged from 1 to 7.68, indicating a low pollution level. However, the polymer risk index indicated that microplastic pollution in Laizhou Bay was at high risk, and PU and polyvinyl chloride were identified as the primary high-risk sources. This study systematically analyzed the composition, distribution, and multiple source characteristics of MPs in Laizhou Bay. The ecological risks associated with these MPs were assessed through the analysis of pollution load and polymer risk indices. This research offers a valuable dataset and a scientific foundation for understanding and managing MP pollution in semi-enclosed marine environments.

The high economic cost of biological invasions in China - Yuanyi Li; Jinyu Zhang; Jun Zhang; Jiacong Du; Ruxiang Yang; Meiling Niu; Yiming Li (Journal of Environmental Management, 2025)

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

Towards robust partial nitrification in low-ammonia wastewater: Electrospinning nanofiber composite-enhanced hydrogel beads immobilized comammox Nitrospira - Peng Tang; Liangang Hou; Meiling Yin; Feng Huang; Zhengwei Pan; Tianhao Shi; Jun Li; Yuhan Zhu; Xin Zhang; Peng Gao (Bioresource Technology, 2025)

Breast Cancer Bone Metastasis: Novel Prognostic Biomarkers Identified - Meiling Chu; Yan Zhang; Jie Chen; Hui Cong; Yulian Yin; Hongfeng Chen (Phenomics, 2025)

Brassinosteroids promote adventitious rooting in marigold via modulating rooting-related enzyme activities, plant hormone and nutrient contents - Yuzheng Deng; Chunlei Wang; Lizhen Luo; Kangding Yao; Meiling Zhang; Weibiao Liao (Horticulture, Environment, and Biotechnology, 2025)

Environment disturbances influence bacterial diversity, structure and co-occurrence network in the Digitaria sanguinalis rhizosphere - Yiming Dai; Ye Cui; Qingchen Xiao; Meiling Ping; Yiming Zhang; Shiguang Hu; Hao Chen; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2025)

Oxidation temperature-dependency of relative dielectric constant and reflective characteristics of lignite and bituminous coal in the presence of very high frequency to ultra-high frequency bands - Qi Liao; Meiling Zhu; Kejiang Lei; Huijie Wei; Minbo Zhang; Haoran Wang; Jin Xu (Fuel, 2025)

CO2 selective adsorption from CO2/CH4 mixtures and regeneration of X zeolites by Li and K modification using various regeneration strategies - Yongbiao Sun; Hui Li; Haijun Lai; Yan Yu; Meiling Hou; Chao Fu; Zaizhou Wang; Chunxiang Zhang (Chemical Engineering Journal, 2025)

Three birds with one stone: a facile superparamagnetic aptasensor for selective capture, dual-mode detection and efficient elimination of methicillin-resistant Staphylococcus aureus - Fengfeng Zhao; Yuming Yao; Shuo Ma; Jiwei Wang; Abudushalamu GuliNaizhaer; Meiling Zhou; Yaya Chen; Xun Gao; Xiaobo Fan; Chen Zhang; Xinglu Jiang; Guoqiu Wu (Chemical Engineering Journal, 2025)

Confining PMo12 in flexible nanocages for enhanced electrochemical energy storage - Yuanyuan Yan; Chongji Wang; Yuhang Chen; Cao Wu; Kezhuo Xie; Zhenyu Liu; Tianyuan Zhang; Weifeng Liu; Xuguang Liu; Tian Wang; Zhaofeng Chen; Shengbo Sang; et al. (Chemical Engineering Journal, 2025)

Characteristics and mechanisms of sea (salt) water intrusion in Laizhou City, Shandong Province, China - Linghao Kong; Hongxian Chu; Guohua Hou; Jiao Zeng; Liyuan Zhao; Xiangcai Han; Yachao Li; Faqiao Zhou; Meiling Yin; Xuzhen Zhang (Frontiers in Marine Science, 2025)
Sea (salt) water intrusion is a significant and ongoing geological disaster, and in recent years, it has become a notable concern for Laizhou City, Shandong Province. To identify the characteristics and mechanism of sea (salt) water intrusion in Laizhou City, samples of different types of water bodies (such as seawater, freshwater, slightly brackish water, brackish water, saline water, and brine) were systematically collected from the coastal zone area. The hydrochemical composition and evolution characteristics of the water bodies and the current situation, trends, and causes of sea (salt) water intrusion were analyzed. In 2020, the sea (salt) water intrusion reached 645.76 km 2 (including 151.64 km 2 of serious intrusion area), which is the largest ever recorded. The sea (salt) water intrusion had a strip-sheet distribution. From land to sea, groundwater gradually transitioned from the HCO 3 ·SO 4 ·Cl-Ca type to SO 4 ·Cl-Na·Ca and SO 4 ·Cl-Na types and then evolved to the Cl-Na type. Furthermore, from land to sea, the dominant cations and anions shifted from Ca 2+ and HCO 3 - to Na + and Cl - . The influence of seawater or brine gradually increased, that of Ca 2+ and HCO 3 - gradually decreased; whereas that of Cl - and Na + gradually increased, showing a division zone of freshwater → slightly brackish water → brackish water → saline water → seawater (brine) in the macroscopic territory. The freshwater, slightly brackish water, and brackish water bodies in the study area were controlled by evaporation and concentration processes and rock weathering leaching, whereas the saline water and brine were primarily controlled by evaporation and concentration processes. Groundwater salinity in the study area mainly originates from sea (salt) water intrusion, and locally groundwater salinity mainly originates from mineral dissolution or human activities. In addition, significant cation exchange adsorption occurred in slightly brackish and brackish water. Overall, these results will help to prevent and control seawater intrusions and improve disaster management.

Oxygen-containing functional groups of biochars enhancing the oxygen release of CaO2 and the generation of free radicals - Qiang Hu; Junheng Zhang; Yadi Pan; Kuan Ding; Chaoyang Xu; Jinyu Hou; Wuxing Liu; Chanchana Thanachayanont; Thipjak Na Lampang; Meiling Chen; Shu Zhang (Process Safety and Environmental Protection, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Spatiotemporal impacts of scientific and technological innovation and industry chain resilience on ecological Efficiency: Evidence from 284 Chinese cities - Meiling Wu; Wei Liu; Rongguang Zhang; Zhiran Fan; Xueyan Zhong (Journal of Environmental Management, 2025)

Characteristics and mechanism of paclobutrazol degradation by the novel bacterial strain Kurthia gibsonii CGMCC 32305 - Wenxin Zhang; Meiling Shi; Yue Lou; Xinyi Liu; Xiaoli Dai; Yang Liu; Zhaoyu Li; Xu Su; Jiajia Li; YongQiang Tian (Journal of Environmental Chemical Engineering, 2025)

Altering wilting time and chopping length to optimize Medicago polymorpha L. fermentation ripening rate and flavour - Ning Mao; Hanyu Zhang; Ermei Du; Meiling Fan; Shihao Liu; Chaosheng Liao; Chao Chen; Hong Sun; Yulong Zheng; Ping Li; Yixiao Xie (Food Bioscience, 2025)

Microbial mechanism and CO2 emission from coastal saline soil: The role of corn stover and nutrient additions - Qiao Xu; Ling Zhang; Yingdong Zhao; Caixian Tang; Yinjuan Li; Meiling Xu; Xiaozhi Wang (Environmental Research, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Effects of carbon sources on nitrite removal and microbial diversity in mariculture water - Zhen Ding; Meiling An; Hongli Xu; Zhongping Xu; Ning Fu; Lushan Wang; Li Zhang; Guoping Li (Biologia, 2025)

Recycling of waste denim: A stepwise utilisation strategy for clean decolourisation, opening and degradation - Zhao Li; Meiling Zhang; Fei Li; Sheng Shi; Shuhua Wang; Chengyong Gao; Yiming Li (Waste Management, 2025)

Copper oxide nanoparticles disrupt lysosomal function and promote foam cell formation in RAW264.7 macrophages - Yilin Luo; Kun Zhang; Lejiao Mao; Meiling Tan; Xiaomei Dong; Na Li; Yuexing Zhou; Chengzhi Chen; Zhen Zou; Jun Zhang (Toxicology, 2025)

RealFusion: A reliable deep learning-based spatiotemporal fusion framework for generating seamless fine-resolution imagery - Dizhou Guo; Zhenhong Li; Xu Gao; Meiling Gao; Chen Yu; Chenglong Zhang; Wenzhong Shi (Remote Sensing of Environment, 2025)

Enhanced hydrogen storage performance of Mg(BH4)2 with in-situ generated TiO2 and TiH2 catalysts - Zhenxuan Ma; Jiaguang Zheng; Ao Xia; Qingbo Zhang; Meiling Lv; Cong Li; Panpan Zhou (Chemical Engineering Journal, 2025)

Spatiotemporal changes of vegetation in the northern foothills of Qinling Mountains based on kNDVI considering climate time-lag effects and human activities - Lili Chen; Zhenhong Li; Chenglong Zhang; Xinxin Fu; Jiahao Ma; Meiling Zhou; Jianbing Peng (Environmental Research, 2025)

Construct favorable solid electrolyte interphase by applying alternating current discharge during battery formation - Yulong Zhang; Shiyou Li; Meiling Wu; Lijuan Wang; Ning He; Yin Quan; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2025)

NIR-activated endoplasmic reticulum stress amplifier to regulate phagocytosis for macrophage-mediated cancer immunotherapy - Yaru Zhang; Wenyu Xie; Jiamin Luo; Rui Gao; Zhimin Gao; Xinyi Wang; Yongxin Huang; Chen Lin; Meiling Tan; Zhiyao Hou (Chemical Engineering Journal, 2025)

Deep Learning Imaging-Based Reconstruction Improved the Image Quality of Synthetic High B-Value DWI for Prostate Lesion Detecting - Xiuxiu Zhou; Hanxiao Zhang; Song Jiang; Jiankun Dai; Lingling Gu; Pei Zhang; Ye Fu; Jie Shi; Xinyi Wan; Meiling Xu; Shiyuan Liu; Li Fan (Journal of Medical and Biological Engineering, 2025)

Anemarrhenae rhizoma combined with Trichosanthis radix ameliorated type 2 diabetes in rats via the PI3K-Akt signalling pathway based on network pharmacology analysis - Yan Lin; Jinde Zheng; Xinyi Zhao; Bei Zheng; Ying Li; Wenjuan Yang; Bing Han; Hanxiao Tang; Meiling Zhang (Natural Product Research, 2025)

A Hypothetical Protein Fragment from Large Yellow Croaker (Larimichthys crocea) Demonstrates Significant Activity Against Both Bacterial and Parasite - Chunmei Yan; Meiling Chen; Hao Xu; Jian Jin; Xiande Liu; Zhiyong Wang; Dongling Zhang (Fishes, 2025)
Antimicrobial peptides (AMPs) are biocompatible and biodegradable, making them an attractive alternative to traditional antimicrobial agents and chemical preservatives. Here, a novel α-helix amphiphilic anionic AMP Lc149 was screened from a large yellow croaker (Larimichthys crocea) using a Bacillus subtilis expression system. Lc149 is a hypothesized protein fragment not annotated in the genome of a large yellow croaker. Both extracellular protein and recombinant Lc149 (rLc149) exhibited significant killing effects against Gram-negative Escherichia coli and Vibrio harveyi. Scanning and transmission electron microscopy revealed that rLc149 had the ability to disrupt bacterial cell membranes, causing irregular cell morphology, severe cell membrane damage, cytoplasm agglutination, and intracellular content leakage. Confocal laser scanning microscopy and flow cytometry further confirmed bacterial cell destruction and mortality rates of over 80%. Gel retardation assays and SDS-PAGE electrophoresis showed that rLc149 was unable to bind to bacterial DNA, but did reduce bacterial protein contents. Additionally, rLc149 maintained antibacterial activity against E. coli and V. harveyi upon exposure to temperatures of 25–100 °C, UV radiation time of 0–60 min, pH levels of 3–12, and different proteases. Biosafety assays revealed low hemolytic toxicity to erythrocytes of large yellow croaker, rabbit, and shrimp, and low cytotoxicity to large yellow croaker kidney cells and HEK 293T cells. More deeply, rLc149 also possessed significant killing activity against parasites. Therefore, rLc149 can be considered an antibacterial and antiparasitic drug in fisheries.

Unraveling the effects of extreme heat conditions on urban heat environment: Insights from local climate zones and integrated temperature data - Bin Wang; Meiling Gao; Yumin Li; Zhenhong Li; Zhenjiang Liu; Xuesong Zhang; Ying Wen (Sustainable Cities and Society, 2025)

Microscale fluvial landscape evolution and its impacts on early human settlement at the Shangshan cultural site in the upper Qiantang region, eastern China - Wenjia Zhang; Zhou Lin; Guoping Zhang; Leping Jiang; Meiling Chen; Shengchao Zhou; Yuchen Zhang; Xiang Zhao (Geomorphology, 2025)

Estimation of winter wheat yield by assimilating MODIS LAI and VIC optimized soil moisture into the WOFOST model - Jing Zhang; Guijun Yang; Junhua Kang; Dongli Wu; Zhenhong Li; Weinan Chen; Meiling Gao; Yue Yang; Aohua Tang; Yang Meng; Zhihui Wang (European Journal of Agronomy, 2025)

Dietary arabinogalactan modulates immunity and improves gut barrier in broilers via regulating metabolome and gut microbiome - Yafei Liu; Qingxiu Liu; Miaolin Ma; Jiatu Zhang; Meiling Liu; Rainer Mosenthin; Lihong Zhao; Shimeng Huang; Qiugang Ma (Carbohydrate Polymers, 2025)

Methyltransferase HsdM Regulates the Pathogenicity of Streptococcus agalactiae to Nile Tilapia (Oreochromis niloticus) - Dongdong Jiang; Bei Wang; Yan Ren; Xubing Mo; Meiling Yu; Defeng Zhang (Fishes, 2025)
DNA methylation is a critical mechanism for regulating gene expression in bacteria and plays an essential role in bacterial pathogenesis. A mutant, WC1535ΔhsdM, lacking hsdM encoding a DNA methyltransferase was constructed using homologous recombination technology. The growth, hemolytic activity, and capsule formation of the mutant were analyzed. The dynamic distribution of the wild-type (WT) and mutant strains in tilapia tissues after artificial infection was determined. The adhesion, invasion, anti-phagocytic, and whole-blood survival abilities of the WT and mutant strains were analyzed. Tilapia were intraperitoneally injected with the WT or mutant strains, and the LD50 values were determined. The expression levels of the immune-related genes in tilapia were analyzed by qRT-PCR. The mutant showed faster growth during the logarithmic growth period (5–10 h) and lower hemolytic activity than the WT strain. Mutant loads in tilapia tissues were significantly lower than those of the WT strain. Mutant strain adhesion to epithelial cells was significantly reduced, it was more easily engulfed by macrophages, and it had decreased intracellular survival. The LD50 of the mutant was 2.06 times higher than that of the WT strain, indicating decreased pathogenicity. Expression levels of immune-related genes IL-1β, IL-6, IFN-γ, and TNF-α in tilapia induced by the mutant were lower than those by the WT strain. In conclusion, the WC1535ΔhsdM mutant exhibited an increased growth rate and decreased hemolytic activity, tissue colonization, and pathogenicity, indicating that HsdM could regulate S. agalactiae growth and pathogenicity. This study provides new insights into the pathogenesis of piscine S. agalactiae.

Advanced treatment of coal to ethylene glycol industry wastewater by catalytic ozonation: Performance and mechanism - Yingying Dong; Lan Yang; Nan Zhang; Ningning Xiao; Yongxia Sun; Ye Yang; Meiling Liu; Zhiwen Chen; Jiangwei Wang; Wendong Wang (Journal of Water Process Engineering, 2025)

Facile solvothermal synthesis of ultrafine platinum nanowires on carbon nanotubes to enhance hydrogen evolution performance - Chang-An Zhou; Meiling Ran; Huixi Chen; Tingting Ma; Chunhui Wu; Hong Zhang; Lei Song; Chao Wang; Kui Ma; Hairong Yue (Fuel, 2025)

Melatonin treatment maintains the quality properties and storability of carambola fruit by modulating energy metabolism - Ting Hu; Shaojie Zheng; Qingqing Liu; Meiling Li; Jingyuan Chen; Huili Zhang; Mengshi Lin; Hetong Lin; Yihui Chen (Food Chemistry, 2025)

Influence of calcium carbonate on ferrihydrite bio-transformation and associated arsenic mobilization/redistribution - Bowei Zhang; Meiling Yin; Kun Gao; Zhi Dang; Chongxuan Liu (Environmental Pollution, 2025)

Birnessite enhanced Cr(III) oxidation during subsurface geochemical processes: Role of Mn(III)-induced nonphotochemical reactive oxygen species - Yuting Zhou; Chuling Guo; Yanping Deng; Yanjun Jiang; Meiling Yin; Kai Chen; Siyu Zhang; Guining Lu; Zhi Dang (Environmental Pollution, 2025)

Abnormal sensory processing cortex in insomnia disorder: a degree centrality study - Hui Wang; Haining Li; Ziyi Liu; Chiyin Li; Zhaoyao Luo; Wei Chen; Meiling Shang; Huiping Liu; Fatemeh Naderi Nejad; Yuanping Zhou; Ming Zhang; Yingxiang Sun (Brain Imaging and Behavior, 2025)

Acrylamide drives amidase-mediated gut dysbiosis to aggravate colitis - Daotong Li; Yinghua Luo; Huimin Fan; Li Dong; Xiaoying Zhang; Yu Feng; Meiling Tian; Shuqing Zhang; Wenjing Chen; Lujia Zhang; Jianwei Gao; Xiangning Ma; et al. (Science Bulletin, 2025)

Highly selective capture of Ni2+ from complex environments by a sandwich-like layered metal sulfide ion exchanger - Mingdong Zhang; Qisheng Hong; Yuan Aocheng; Yan Zhang; Xiaoying Huang; Meiling Feng; Jingli Mu (Journal of Hazardous Materials, 2025)

Improving the functional components and biological activities of navel orange juice through fermentation with an autochthonous strain Lactiplantibacillus paraplantarum M23 - Meiling Huang; Chunling Lai; Yan Liang; Qin Xiong; Chaoyun Chen; Zhiran Ju; Yueming Jiang; Jun Zhang (Food and Bioproducts Processing, 2025)

Combined Effects of Cadmium and Lead on Growth Performance and Kidney Function in Broiler Chicken - Man Zhao; Longqiang Xie; Wenbin Huang; Meiling Li; Xin Gu; Wei Zhang; Jintao Wei; Niya Zhang (Biological Trace Element Research, 2025)

Dual-mode detection of human immunoglobulin via copper oxide nanozyme catalysis fluorescent species generation and photoelectrochemical alteration in ZnIn2S4/SnO2-based system - Jiawei Zhou; Lili Zhao; Yuee Zhong; Peipei Li; Xiaohua Zhu; Shu Huang; Youyu Zhang; Meiling Liu (Analytica Chimica Acta, 2025)

Bacillus subtilis 2118 exhibits bactericidal activity due to an inserted fish cDNA library - Chunmei Yan; Meiling Chen; Jian Jin; Xiande Liu; Zhiyong Wang; Yongju Luo; Dongling Zhang (Aquaculture, 2024)

A mini-review on polyvinyl alcohol/lignin (nano)composites: Preparation, applications and perspectives - Meiling Han; Yu Zhang; Ying Zhang; Qing Ye; Mika Sillanpää; Xinli Zhu; Weijun Yang (Sustainable Chemistry and Pharmacy, 2024)

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Preparation of hydrophilic pulp cellulose-based membrane and its performance in oil-water separation - Qing Liu; Guorui Li; Kehui Qi; Huihui Zhang; Meiling Pu; Lu Li; Yanju Lu (Journal of Water Process Engineering, 2024)

Investigating CO₂ sequestration via enhanced rock weathering: Effects of temperature and citric acid on dolomite and basalt - Qiao Xu; Feifan Zhang; Fanhao Song; Hongyan Guo; Xiaozhi Wang; Fenfen Bi; Meiling Xu (Journal of Cleaner Production, 2024)

Visible-light-assisted peroxymonosulfate activation using MIL-88A(Fe)/BiOI heterojunction composite to drive charge transport for eliminating acid red 18 - Meiling Wang; Xiaochun Liu; Kebin Li; Wenting Huo; Hong Wei; Hongna Zhang; Nannan Zhong; Hai-Ying Jiang (Journal of Environmental Chemical Engineering, 2024)

Similarity recognition approach to identify zero-added MSG soy sauce using stable isotopes and amino acid profiles - Chunlin Li; Meiling Sheng; Menglin Zhang; Karyne M. Rogers; Jing Nie; Shengzhi Shao; Jianbo Xiao; Yuwei Yuan (Food Chemistry, 2024)

Fermentation by Penicillium polonicum improves the functional components and biological effects of orange peel via producing β-glucosidase without the risk of potential mycotoxins - Yan Liang; Chunling Lai; Liangliang Gao; Qingna Wu; Meiling Huang; Yueming Jiang; Jun Zhang (Food Bioscience, 2024)

Bacteria contribute more than fungi to SOC decomposition in a paddy field under long-term free-air CO2 enrichment - Meiling Xu; Feifan Zhang; Ling Zhang; Hongze Zhang; Caixian Tang; Xiaozhi Wang; Jing Ma; Qiao Xu (European Journal of Soil Biology, 2024)

MicroRNA expression profiles in plasma exosomes of late pregnant giant pandas - Meiling Cheng; Yingmin Zhou; Qian Wang; Bo Luo; Yanwu Lai; Jianbin Cheng; Xiuyue Zhang; Yan Huang; Desheng Li (Molecular Biology Reports, 2024)

Comparative karyotype analysis provides cytogenetic evidence for the origin of sweetpotato - Jianying Sun; Qian Zhang; Meiling Xu; Mengxiao Yan; Xingyu Liu; Jian Sun; Qinghe Cao; Hongxia Wang; Jun Yang; Zongyun Li; Yonghua Han (Chromosome Research, 2024)

Unravelling spermatogenesis in spotted wolffish: Insights from the ultrastructure of juvenile male testes to the cryopreservation of broodstock sperm - Joshua Superio; Julien Resseguier; Rafael Henrique Nobrega; Caroline M. Grebstad; Ioannis Fakriadis; Atle Foss; Ørjan Hagen; Meiling Zhang; Maria del Pilar García-Hernández; Jorge Galindo-Villegas (Aquaculture, 2024)

Analytical and numerical study on the dynamic responses of the buried offshore oval lined-pipeline system under strike-slip fault - Zhaochao Li; Shiyi Zhang; Meiling Shen; Hao Huang (Ocean Engineering, 2024)

Microbial inoculants using spent mushroom substrates as carriers improve soil multifunctionality and plant growth by changing soil microbial community structure - Hui Nie; Chong Li; Zhaohui Jia; Xuefei Cheng; Xin Liu; Qianqian Liu; Meiling Chen; Yong Ding; Jinchi Zhang (Journal of Environmental Management, 2024)

Monthly Precipitation Prediction Based on the CEEMDAN-BMA Model - Youyi Zhao; Shangxue Luo; Jiafang Cai; Zhao Li; Meiling Zhang (Water Resources Management, 2024)

Genomic selection on ear height, plant height and grain yield in the primary testing stage of maize hybrids - Xinying Kong; Shuwen Ji; Yubo Liu; Xuecai Zhang; Meiling Liu; Chen Yue; Ruichen Yang; Cong Li; Xiaomei Dong; Ao Zhang; Yanye Ruan (Euphytica, 2024)

A novel and convenient lying cow identification method based on YOLOX and CowbodyNet: A study with applications in a barn - Jianxing Xiao; Yongsheng Si; Meiling Xie; Gang Liu; Zhang Yan; Kejian Wang (Computers and Electronics in Agriculture, 2024)

PhERF71 regulates petunia flower senescence by modulating ethylene biosynthesis - Xiaotong Ji; Yanxiang Mao; Yanping Yuan; Meiling Wang; Yike Zhao; Lei Zhang; Daoyang Sun (Postharvest Biology and Technology, 2024)

Interfacial charge demulsification endowed dual-network photocatalytic hydrogen-bonded PVA@agarose membranes for oil-water separation - Jing Jing; Zhanjian Liu; Yuxin Fu; Haonan Liu; Xiguang Zhang; Meiling Li; Liyan Liu; Huaiyuan Wang (Journal of Hazardous Materials, 2024)

Development of multi-cross-linking, rapid curing, and easy cleaning, edible hydrogels for meat preservation - Yuxin Cheng; Jiaxin Xu; Rongfan Zhang; Jianguo Lin; Meiling Zhou; Xianmin Qin; Keshan Wang; Ying Zhou; Qiujin Zhu; Yongguo Jin; Yuanyuan Liu (Food Hydrocolloids, 2024)

The role of HMGB2 in the immune response of Nile tilapia (Oreochromis niloticus) to streptococcal infection - Yuhang Dong; Zhiqiang Zhang; Yongxiong Huang; Xuyan Tan; Xing Li; Meiling Huang; Jiaming Feng; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Surface phosphorylated Li5FeO4 prelithiation additive synergistically improves the air-stability and lithium-ion conductivity - Lei Niu; Meiling Wu; Yulong Zhang; Cankun Gao; Xin Li; Hao Ding; Ning He; Peng Wang; Jiawen Zhang; Jingxuan Yan; Ningshuang Zhang; Dongni Zhao; et al. (Chemical Engineering Journal, 2024)

Synergistic enhancement of cadmium immobilization and soil fertility through biochar and artificial humic acid-assisted microbial-induced calcium carbonate precipitation - Yu Li; Meiling Zhang; Xiaobin Wang; Shuang Ai; Xianghui Meng; Zhuqing Liu; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2024)

m6A-mediated HDAC9 upregulation promotes particulate matter-induced airway inflammation via epigenetic control of DUSP9-MAPK axis and acts as an inhaled nanotherapeutic target - Yingying Zeng; Xin Bai; Guiping Zhu; Mengchan Zhu; Wenjun Peng; Juan Song; Hui Cai; Ling Ye; Cuicui Chen; Yuanlin Song; Meiling Jin; Xue-Qing Zhang; et al. (Journal of Hazardous Materials, 2024)

Coupled physicochemical dual-crosslinking Ti3C2T composite aerogels for the selective adsorption of gallium ions in acid fly ash leaching - Xiaopei Zhang; Weifeng Liu; Chang Liang; Dongju Fu; Meiling Wang; Xuguang Liu (Journal of Hazardous Materials, 2024)

Different activation of STAT1 and STAT2 phosphorylation by IFNc, IFNd, and IFNh in tilapia - Qingqing Wen; Shaoshuai Tang; Jingyi Mo; Meiling Zhang; Meng Long; Yishan Lu; Zhen Gan (Fish & Shellfish Immunology, 2024)

Mxene-supported NbVH nanoparticles as efficient catalysts for reversible hydrogen storage in magnesium borohydride - Ao Xia; Jiaguang Zheng; Qingbo Zhang; Meiling Lv; Zhenxuan Ma; Chao Su (Chemical Engineering Journal, 2024)

Phosphorylation of RasGRP1 by Shc3 prevents RasGRP1 degradation and contributes to Ras/c-Jun activation in hepatocellular carcinoma - Xinran Zhang; Yun Liu; Rui Yang; Yuanyuan Guo; Meiling Yan; Ying Xiao; Yunzhuo Dong; Ruixia Zhang; Yinpeng Qin; Yishan Bu; Yi Zhang; Huier Gao (Molecular and Cellular Biochemistry, 2024)

A Profile of Drug-Resistant Mutations in Mycobacterium tuberculosis Isolates from Guangdong Province, China - Chenchen Zhang; Zhuhua Wu; Xinchun Huang; Yuchuan Zhao; Qi Sun; Yanmei Chen; Huixin Guo; Qinghua Liao; Huizhong Wu; Xunxun Chen; Anqi Liang; Wenya Dong; et al. (Indian Journal of Microbiology, 2024)

A new monocyclic monoterpene derivative from volva of Phallus dongsun - Shihao Qian; Guangdi Wang; Meiling Lu; Xian Zhang; Tingchi Wen (Natural Product Research, 2024)

Occupation patterns during the Shangshan in the upper Qiantang River Basin, eastern China: A geomorphic study based on GIS - Wenjia Zhang; Zhou Lin; Leping Jiang; Chao Ding; Meiling Chen; Shengchao Zhou; Xiang Zhao (Quaternary International, 2024)

Post-productivism and rural revitalization in China: Drivers and outcomes - Meiling Wu; Qian Forrest Zhang; John Donaldson (Journal of Rural Studies, 2024)

Effects of microplastics on sedimentary greenhouse gas emissions and underlying microbiome-mediated mechanisms: A comparison of sediments from distinct altitudes - Meiling Yi; Jingnan Liu; Maosen Ma; Sibo Zhang; Xin Chen; Xinghui Xia; Yang Li (Journal of Hazardous Materials, 2024)

Nitric Oxide Promotes Adventitious Rooting in Cucumber Under Drought Stress Through Regulating Ascorbate Glutathione Cycle and Protein S-Nitrosylation - Xuemei Hou; Yuanyuan Dan; Nana Qi; Meiling Zhang; Changxia Li; Yihua Li; Yandong Yao; Weibiao Liao (Journal of Plant Growth Regulation, 2024)

Cellulose nanofibrils-stabilized food-grade Pickering emulsions: Clarifying surface charge's contribution and advancing stabilization mechanism understanding - Yadong Zhao; Feifan Zhang; Meiling Chen; Fei Liu; Bin Zheng; Wenhua Miao; Huimin Gao; Rusen Zhou (Food Hydrocolloids, 2024)

Identification and functional characterization of interleukin-22 (IL-22) in orange-spotted grouper (Epinephelus coioides) - Dapeng Yu; Guanjian Yang; Jingyi Mo; Meiling Zhang; Hongli Xia; Zhen Gan; Yishan Lu (Fish & Shellfish Immunology, 2024)

Subalpine peatland development since the Last Glacial Maximum in subtropical China: Predominantly controlled by monsoonal climate and local topography - Cong Chen; Kangyou Huang; Dehao Xie; Meiling Man; Yongjie Tang; Yuanfu Yue; Xiao Zhang; Zhuo Zheng; Rachid Cheddadi (CATENA, 2024)

Microbial role in enhancing transfer of straw-derived nitrogen to wheat under nitrogen fertilization - Shuyu Huang; Xue Gao; Li Zeng; Meiling Zhang; Liyu Zhang; Shiyu Wang; Yuanzheng Zhao; Wei Zhou; Chao Ai (Soil and Tillage Research, 2024)

Histological and single-nucleus transcriptome analyses reveal the specialized functions of ligular sclerenchyma cells and key regulators of leaf angle in maize - Qibin Wang; Qiuyue Guo; Qingbiao Shi; Hengjia Yang; Meiling Liu; Yani Niu; Shuxuan Quan; Di Xu; Xiaofeng Chen; Laiyi Li; Wenchang Xu; Fanying Kong; et al. (Molecular Plant, 2024)

Novel superhydrophobic sponge with flower-like architecture for oily emulsion separation and organic pollutants photodegradation - Jinyue Yang; Zhanjian Liu; Jing Jing; Xiguang Zhang; Yuxin Fu; Meiling Li; Huaiyuan Wang (Journal of Environmental Chemical Engineering, 2024)

Unlocking high-value components from Brewer's spent yeast for innovative food applications - Guozheng Wei; Wenqi Shang; Zhengjie Xie; Mengran Zhang; Meiling Dan; Guohua Zhao; Damao Wang (Food Bioscience, 2024)

Subchronic co-exposure of polystyrene nanoplastics and 3-BHA significantly aggravated the reproductive toxicity of ovaries and uterus in female mice - Guanghua Xiong; Haiyan Zhang; Yulin Peng; Huangqi Shi; Meiling Han; Tianle Hu; Hongcheng Wang; Shangrong Zhang; Xiaoqing Wu; Gaoxiao Xu; Jun'e Zhang; Yong Liu (Environmental Pollution, 2024)

A jellyfish robot based on two-bar and four-spring tensegrity structures - Jianwei Sun; Changjian Li; Meiling Zhang; Lu Shen; Siyang Gao (Ocean Engineering, 2024)

Enhanced reversible hydrogen storage in LiBH4-Mg(BH4)2 composite with V2C-Mxene - Qingbo Zhang; Jiaguang Zheng; Ao Xia; Meiling Lv; Zhenxuan Ma; Meijia Liu (Chemical Engineering Journal, 2024)

Resting-state EEG Microstate Features Can Quantitatively Predict Autistic Traits in Typically Developing Individuals - Huibin Jia; Xiangci Wu; Xiaolin Zhang; Meiling Guo; Chunying Yang; Enguo Wang (Brain Topography, 2024)

The short-term effect of simulated acid rain and nitrogen deposition on the soil microbial functional profile targeting C, N, and P cycling - Chong Li; Yong Ding; Shuifeng Zhang; Meiling Chen; Yuhao Wang; Zhaohui Jia; Shilin Ma; Jinchi Zhang; Xin Liu (Applied Soil Ecology, 2024)

Green and efficient approach to extract bioactive flavonoids with antioxidant, antibacterial, antiglycation, and enzyme inhibitory activities from navel orange peel - Chunling Lai; Meiling Huang; Qin Xiong; Yan Liang; Yueming Jiang; Jun Zhang (Sustainable Chemistry and Pharmacy, 2024)

Microbial features with uranium pollution in artificial reservoir sediments at different depths under drought stress - Siyu Liu; Juan Liu; Jingye She; Zhenyu Xie; Lei Zhou; Qunwei Dai; Xing Zhang; Yuebing Wan; Meiling Yin; Xinjiao Dong; Min Zhao; Diyun Chen; et al. (Science of The Total Environment, 2024)

Identification of dynamic changes in volatile compounds and metabolites during the smoking process of Zhenba bacon by GC-IMS combined metabolomics - Shuai Han; Meiling Ke; Ling Wang; Haidong Ma; Guofei Wu; Lianxu Zhu; Tao Zhang; Hongzhao Lu (Food Research International, 2024)

MnO2 nanozyme with lanthanide-based radiosensitization for advanced radiotherapy by tumor microenvironment triggering STING pathway activation - Meiling Tan; Zhimin Gao; Xiaozhao Wang; Chen Lin; Yuchi Wan; Wenyu Xie; Wei Chen; Yaru Zhang; Zewei Quan; Zhiyao Hou (Chemical Engineering Journal, 2024)

Synchronized achieving amount reduction and efficiency increase of lithium salt-type additive by alternating current pulse discharge technology - Shiyou Li; Yulong Zhang; Shumin Wu; Yin Quan; Meiling Wu; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2024)

Pt,P-codoped carbon nitride nanoenzymes for fluorescence and colorimetric dual-mode detection of cholesterol - Meiling Chen; Yang Yang; Qinhua Chen; Lina Tang; Junlin Liu; Yujie Sun; Qiming Liu; Yulin Zhang; Guo-jun Zhang; Shaowei Chen (Analytica Chimica Acta, 2024)

Minocycline attenuates the bilirubin-induced developmental neurotoxicity through the regulation of innate immunity and oxidative stress in zebrafish embryos - Guanghua Xiong; Tianle Hu; Yihong Yang; Haiyan Zhang; Meiling Han; Jiahao Wang; Yipeng Jing; Hongbo Liu; Xinjun Liao; Yong Liu (Toxicology and Applied Pharmacology, 2024)

A novel method to advance the brGDGTs-based paleoclimate reconstruction applicable to different terrestrial environments - Liping Tian; Mengyuan Wang; Cong Chen; Xiao Zhang; Zhuo Zheng; Meiling Man; Kangyou Huang; Li Li; Guodong Jia (Quaternary Science Reviews, 2024)

Effects of butyl paraben on behavior and molecular mechanism of Chinese striped-necked turtle (Mauremys sinensis) - Xia Wu; Ijaz Khan; Xiaoqi Ai; Jiliang Zhang; Haitao Shi; Ding Li; Meiling Hong (Aquatic Toxicology, 2024)

Increased black carbon (soot) accumulation during the Anthropocene in a less-developed region of Xinjiang, northwestern China - Dewen Lei; Yongming Han; Changlin Zhan; Chong Wei; Yalan Tang; Meiling Guo; Jianing Zhang; Jingyu Li (Anthropocene, 2024)

Shaking table tests of a switching power cabinet considering physical damage and functionality loss - Haopeng Zuo; Guoliang Sun; Pengbo Zhang; Meiling Wang; Jichao Li; Qingxue Shang; Tao Wang (Soil Dynamics and Earthquake Engineering, 2024)

Illuminated fulvic acid stimulates denitrification and As(III) immobilization in flooded paddy soils via an enhanced biophotoelectrochemical pathway - Yanqiong Zeng; Honghui Wang; Jiehua Hu; Jing Zhang; Feng Wang; Tongyu Wang; Qiqi Zhou; Randy A. Dahlgren; Meiling Gao; Hui Gao; Zheng Chen (Science of The Total Environment, 2024)

Using low-protein diet in egg production for win-win of productivity and environmental benefits should be prudent: Evidence from pilot test - Meiling Liu; Shunju Geng; Qingfeng Wang; Jinqiu Mi; Lihong Zhao; Jianyun Zhang; Cheng Ji; Hongliang Wang; Qiugang Ma; Shimeng Huang (Science of The Total Environment, 2024)

Unraveling seasonal shifts in microbial and geochemical mediated arsenic mobilization at the estuarine sediment-water interface under redox changes - Liqin Duan; Jinming Song; Yuting Zhang; Meiling Yin; Huamao Yuan; Xuegang Li (Science of The Total Environment, 2024)

Molecular characteristics and functional analysis of non-specific cytotoxic cell receptor (NCCRP1) in golden pompano (Trachinotus ovatus) - Meiling Huang; Zhiqiang Zhang; Xing Li; Jiamin Feng; Yongxiong Huang; Amoah Kwaku; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

A prototype galectin-1 (also known as galecin-2) from large yellow croaker (Larimichthys crocea): Molecular and function study - Xin Tang; Zhiqun Xiao; Meiling Chen; Jian Jin; Chunmei Yan; Xingcheng Zhu; Zhiyong Wang; Dongling Zhang (Fish & Shellfish Immunology, 2024)

Metagenomic binning analyses of swine manure composting reveal mechanism of nitrogen cycle amendment using kaolin - Huakang Li; Zixuan Zhao; Meiling Shi; Bin Luo; Guangdong Wang; Xiaojuan Wang; Jie Gu; Zilin Song; Yifan Sun; Li Zhang; Jia Wang (Bioresource Technology, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Isolation, heterologous expression, and functional determination of an iron regulated transporter (IRT) gene involved in Fe2+ transport and tolerance to Fe2+ deficiency in Vitis vinifera - Zhizhong Song; Xue Wang; Mengyuan Li; Youzheng Ning; Shengpeng Shi; Guangrong Yang; Hongxia Zhang; Meiling Tang; Bin Peng (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
In plants, iron (Fe) regulated transporters (IRT) play important roles in uptake and transport of Fe that contributes to plant growth and development. However, biological functions of IRT transporters in fruit trees are still unknown. This study isolated 10 VvIRT genes from ‘Marselan’ grape, with varying expression levels across different tissues/organs, particularly enhanced under Fe depletion, especially in roots. Notably, VvIRT7 is the most abundantly expressed IRT gene in grape, beneficially restoring the Fe 2+ uptake defect of yeast mutant DEY1453. Furthermore, VvIRT7 showed dominant expression in the roots of irt1 /35S:: IRT7 complementation lines. Overexpressing of VvIRT7 rescued the retarded growth of irt1 knockout mutant, by increasing the fresh weight, dry weight, total root length, total root surface, lateral root numbers, total leaf chlorophyll, ACO activity, NiR activity, SDH activity, and tissue Fe concentration. This study provides insights for understanding molecular mechanisms of Fe uptake and transport in grape.

Migration and transformation of soil phosphorus by organic acids: a global meta-analysis - Ying Zhao; Meiling Zhang; Zhuqing Liu; Fan Yang (Journal of Soils and Sediments, 2024)

Morphological and transcriptomic analyses of embryonic development of red-eared slider Trachemys scripta elegans - Jing Lin; Miaomiao Zhang; Fangbin Liang; Yunfang Ni; Jiani Zhang; Haitao Shi; Meiling Hong; Li Ding (Animal Reproduction Science, 2024)

Control of citrus blue and green molds by Actinomycin X2 and its possible antifungal mechanism - Liangliang Gao; Yan Liang; Qin Xiong; Meiling Huang; Yueming Jiang; Jun Zhang (Pesticide Biochemistry and Physiology, 2024)

The stable carbon and hydrogen isotopic composition of microbial fatty acids traces microbial metabolism in soils and peats - Yiming Zhang; B. David A. Naafs; Xianyu Huang; Meiling Zhao; Linghan Zeng; Jerome Blewett; Richard D. Pancost; Shucheng Xie (Geochimica et Cosmochimica Acta, 2024)

In situ formation of fluorescence species for the detection of alkaline phosphatase and organophosphorus pesticide via the ascorbate oxidase mimetic activity of AgPd bimetallic nanoflowers - Luo Luo; Jing Liu; Yani Liu; Haoyu Chen; Youyu Zhang; Meiling Liu; Shouzhuo Yao (Food Chemistry, 2024)

A Fe-Ni-MOF-74@bamboo photothermal evaporator for efficient solar steam generation - Yiduo Chen; Dongxu Gu; Yujuan Zhao; Chaowei Zhang; Meiling Li; Qi Zhou; Yonghui Lin; Yaru Gong; Zhongmin Su; Weiting Yang (Desalination, 2024)

Silver nanowire-infused carbon aerogel: A multifunctional nanocellulose-derived material for personal thermal management - Meiling Zhang; Yinan Fan; Ni Wang; Hongguo Gao; Lei Zhang; Yanjiao Zhao; Lifang Liu (Carbohydrate Polymers, 2024)

Microbial ecological clusters structured by environments drive maize residue decomposition at the continental scale - Meiling Zhang; Shiyu Wang; Liyu Zhang; Wentao Li; Mengmeng Cao; Shuyu Huang; Xinpeng Xu; Ping He; Wei Zhou; Laurent Philippot; Chao Ai (Science of The Total Environment, 2023)

Long-term performance of ZVI-stimulating anaerobic/aerobic system - PEI modified ceramic membrane SMBR in reusing food wastewater for irrigation: An industrial project and microbial community shift - Chunyan Wang; Leyong Jiang; Meiling Hu; Cong Wang; Yongzhen Peng; Shujun Zhang; Weikang Qi (Journal of Water Process Engineering, 2023)

Synthesis of MnOOH-hydroxyapatite nanowires for degradation of tetracycline - Shenglan Zhao; Meiling Zhou; Jiarui Ren; Yaping Zhang; Yufeng He; Rongmin Wang (Journal of Environmental Chemical Engineering, 2023)

Dual responsive cellulose-based fluorescent material fabricated in a CO2 switchable solvent for multifunctional applications - Yiting Xu; Xiaobo Yu; Meiling Chen; Yi Sun; Wei Zhang; Yajin Fang; Lanyun Fang; Haining Na; Fei Liu; Jin Zhu (Chemical Engineering Journal, 2023)

Scalable fabrication of a robust asymmetric superwetting Janus mesh by facile spray-coating for oil–water emulsions separation - Jing Jing; Zhanjian Liu; Xiguang Zhang; Jinyue Yang; Meiling Li; Ruixia Yuan; Guolin Jing; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

A halogen-free hyper-crosslinked ionic polymer for efficient multi-conversion of CO2 into carbonates under mild conditions, with a combination of theoretical study - Bowen Jiang; Jia Liu; Wenjie Xiong; Meiling Weng; Jigang An; Yuewei Fan; Leizhi Zheng; Guoqiang Yang; Zhibing Zhang (Chemical Engineering Journal, 2023)

Nanocomposite hydrogel to deliver the immunomodulator lenalidomide and anti-inflammatory hesperidin locally to joints affected by rheumatoid arthritis - Xingjie Du; Yan Lin; Zheyu Shuai; Junfeng Duan; Changguang Wang; Junsheng Liu; Jun Jiang; Jianming Wu; Meiling Zhou; Zhirong Zhang; Zhongbing Liu; Xiangyu Zhou; et al. (Chemical Engineering Journal, 2023)

Investigating the effects of organic amendments on soil microbial composition and its linkage to soil organic carbon: A global meta-analysis - Jiwen Cui; Binggeng Yang; Meiling Zhang; Dali Song; Xinpeng Xu; Chao Ai; Guoqing Liang; Wei Zhou (Science of The Total Environment, 2023)

Thermo-responsive ion imprinted polymer on the surface of magnetic carbon nanospheres for recognizing and capturing low-concentration lithium ion - Chang Liang; Xiaopei Zhang; Weifeng Liu; Xingfu Song; Shuying Sun; Dongju Fu; Geng Dong; Meiling Wang; Yonghui Bai; Xuguang Liu (Minerals Engineering, 2023)

Designing a cercosporin-bioinspired bifunctional algicide with flocculation and photocatalysis for efficiently controlling harmful cyanobacterial blooms - Zhenbo Yuan; Meiling Liu; Zengping Su; Huibin Xu; Changmei Liu; Liushen Lu; Lingling Wang; Xiaonan Zhu; Yan Zhang; Yijian Rao (Journal of Hazardous Materials, 2023)

Interleukin-8 involved in Nile Tilapia (Oreochromis niloticus) against bacterial infection - Xing Li; Baijian Jiang; Zhiqiang Zhang; Meiling Huang; Jiamin Feng; Yongxiong Huang; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Exposure to ambient air pollutants is associated with an increased incidence of hyperuricemia: A longitudinal cohort study among Chinese government employees - Lidan Duan; Muyang Zhang; Yuhan Cao; Yuwei Du; Meiling Chen; Rumeng Xue; Minxue Shen; Dan Luo; Shuiyuan Xiao; Yanying Duan (Environmental Research, 2023)

Metabolic profiling of Apostichopus japonicus body wall exposed to a typical type of PBDEs: potential health risks and impact on sea cucumber health - Kui Ding; Pengji Zhuo; Meiling Ge; Xiaomei Liao; Jing Mo; Shilin Liu; Qinzeng Xu; Xuelei Zhang (Frontiers in Marine Science, 2023)
Introduction Sea cucumbers are cultivated mainly for their valuable body wall. Polybrominated diphenyl ethers are common persistent pollutants in sea waters with known impacts on aquatic animals nonetheless not yet studied for the body wall of sea cucumbers. Methods Using ltra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Triple-TOF-MS), we investigated the metabolic impact of 2,2',4,4'-tetrabromodiphenyl ether (BDE-47) on the body wall of Apostichopus japonicus . etabolite changes and metabolic pathway alterations were assessed in response to three distinct concentrations of BDE-47: 0.1 µg/L, 1.0 µg/L, and 10.0 µg/L. REsults Exposure to BDE-47 led to notable alterations in the metabolic profiles of the body wall. A total of 95~102 metabolites in the 0.1 ~ 10.0 µg/L BDE-47 treated group were altered significantly, and various disrupted metabolic pathways were identified and characterized. These metabolites and metabolic pathways were mainly involved in lipid metabolism, energy metabolism, immunity, oxidative stress, inflammation, and neurotoxicity. Discussion The findings of our study shed light on the potential health risks that polybrominated diphenyl ethers present to sea cucumbers. This underscores the imperative for both researchers and policymakers to delve deeper into further investigations and studies. These results indicate the necessity for enhanced monitoring and management practices within the sea cucumber aquaculture industry to mitigate the impact of these persistent organic pollutants and protect the health and safety of this valuable resource.

Study on optimization of shelter locations and evacuation routes of gas leakage accidents in chemical industrial park - Di Zhang; Zhanli Mao; Meiling Gong; Jianxing Ren; Songtao Zuo; Xin Chen (Process Safety and Environmental Protection, 2023)

Dose-response relationship of elements with blood lipids and the potential interaction: A cross-sectional study from four areas with different pollution levels in China - Shaoyi Chen; Muyang Zhang; Lidan Duan; Meiling Chen; Yuwei Du; Yuhan Cao; Zhijun Huang; Jia Zhao; Yanying Duan (Journal of Trace Elements in Medicine and Biology, 2023)

Reservoir water flooding evaluation based on electromagnetic wave logging permittivity and conductivity inversion - Yi Xiaodong; Zhang Meiling; Qin Lianbin; Lin Jianhua (Journal of Applied Geophysics, 2023)

Savanna/rainforest dynamics and hydroclimate changes in northern boundary of tropical Asia over the past 150 kyrs - Cong Chen; Kangyou Huang; Zhuo Zheng; Yongqiang Zong; Peter Kershaw; Shixiong Yang; Liping Tian; Meiling Man; Sheng-Hua Li; Chris Brodie; Ning Wang; Xiao Zhang; et al. (Global and Planetary Change, 2023)

Oil occurrence state and quantity in alkaline lacustrine shale using a high-frequency NMR technique - Chenxi Zhang; Fujie Jiang; Tao Hu; Di Chen; Liliang Huang; Zhenxue Jiang; Xiaohao Wang; Zheyu Liu; Yuping Wu; Jiahao Lv; Renda Huang; Meiling Hu; et al. (Marine and Petroleum Geology, 2023)

Involvement of CD27 in innate and adaptive immunities of Nile tilapia (Oreochromis niloticus) - Baijian Jiang; Qi Li; Zhiqiang Zhang; Yongxiong Huang; Yiqin Wu; Xing Li; Meiling Huang; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Ag2S QDs integration with MnO2 nanosheets for the sensitive detection of Cr (VI) via the redox reaction induced photoelectrochemical variation - Lili Zhao; Haoyu Chen; Ying Tang; Peipei Li; Xiaohua Zhu; Jingyi Liu; Meiling Liu; Youyu Zhang; Shouzhuo Yao (Analytica Chimica Acta, 2023)

The positive effects of mineral-solubilizing microbial inoculants on asymbiotic nitrogen fixation of abandoned mine soils are driven by keystone phylotype - Chong Li; Zhaohui Jia; Shuifeng Zhang; Tao Li; Shilin Ma; Xuefei Cheng; Meiling Chen; Hui Nie; Lu Zhai; Bo Zhang; Xin Liu; Jinchi Zhang; et al. (Science of The Total Environment, 2023)

Decomplexation of Ni-EDTA by thermally activated persulfate: Efficiency and mechanism - Xinkai Yuan; Wei Xiong; Yanhua Peng; Bo Li; Jianzhi Zhang; Meiling Chen; Xiuqin Xiong; Liming Yang; Hui Shi; Xubiao Luo; Penghui Shao (Journal of Water Process Engineering, 2023)

Characterisation of kapok fibre's biochar for arsenate adsorption removal from aqueous solution. - Kanfolo Franck Herve Yeo; Yingying Dong; Tongxuan Xue; Zhiwen Chen; Nan Zhang; Ye Yang; Liu Han; Meiling Liu; Ange Nsilani Kouediatouka; Hanse Pablick Patherny Lobo Mouguegue; Wendong Wang (Environmental Research, 2023)

Channel migration in the northeastern margin of the Tibetan Plateau and its implication for fluvial response to the interaction between rapid tectonic activity, climatic fluctuation and human influence - Baotian Pan; Xiaohua Li; Zhenbo Hu; David Bridgland; Qinhong Mo; Zijuan Dong; Menghao Li; Yanan Yang; Rob Westaway; Guanghui Dong; Shanjia Zhang; Meiling Zhong (Quaternary Science Reviews, 2023)

An injectable antibacterial hydrogel to regulate ocular immune for endophthalmitis treatment - Zunzhen Ming; Lin Han; Huanhuan Zhu; Meiyu Bao; Qiangyuan Fan; Shaobo Xue; Kesheng Wang; Yue Zhang; Meiling Lu; Chongshun Xu; Qi Wu; Tingting Li; et al. (Chemical Engineering Journal, 2023)

Lacticaseibacillus casei LH23 Suppressed HPV Gene Expression and Inhibited Cervical Cancer Cells - Shiyue Hu; Yunpeng Hao; Xiao Zhang; Yaping Yang; Meiling Liu; Nan Wang; Tong-Cun Zhang; Hongpeng He (Probiotics and Antimicrobial Proteins, 2023)

Response of microbial communities to nutrient removal in coastal sediment by using ecological concrete - Meiling Zhang; Jiannan Ji; Lemian Liu; Yisong Guo; Jianfeng Chen (Environmental Science and Pollution Research, 2023)

Regulatory role of myo-inositol in the ovarian development of female Chinese mitten crab (Eriocheir sinensis) - Xianyong Bu; Qincheng Huang; Ying Song; Changle Qi; Zhideng Lin; Xiaodan Wang; Meiling Zhang; Chuanjie Qin; Jian G. Qin; Liqiao Chen (Aquaculture, 2023)

Subducted carbonates not required: Deep mantle melting explains stable Ca isotopes in kimberlite magmas - Michael A. Antonelli; Andrea Giuliani; Zaicong Wang; Meiling Wang; Lian Zhou; Lanping Feng; Ming Li; Zhaofeng Zhang; Fang Liu; Russell N. Drysdale (Geochimica et Cosmochimica Acta, 2023)

A Two-Stage Network Based on Transformer and Physical Model for Single Underwater Image Enhancement - Yuhao Zhang; Dujing Chen; Yanyan Zhang; Meiling Shen; Weiyu Zhao (Journal of Marine Science and Engineering, 2023)
The absorption and scattering properties of water can cause various distortions in underwater images, which limit the ability to investigate underwater resources. In this paper, we propose a two-stage network called WaterFormer to address this issue using deep learning and an underwater physical imaging model. The first stage of WaterFormer uses the Soft Reconstruction Network (SRN) to reconstruct underwater images based on the Jaffe–McGramery model, while the second stage uses the Hard Enhancement Network (HEN) to estimate the global residual between the original image and the reconstructed result to further enhance the images. To capture long dependencies between pixels, we designed the encoder and decoder of WaterFormer using the Transformer structure. Additionally, we propose the Locally Intended Multiple Layer Perceptron (LIMP) to help the network process local information more effectively, considering the significance of adjacent pixels in enhancing distorted underwater images. We also proposed the Channel-Wise Self-Attention module (CSA) to help the network learn more details of the distorted underwater images by considering the correlated and different distortions in RGB channels. To overcome the drawbacks of physical underwater image enhancement (UIE) methods, where extra errors are introduced when estimating multiple physical parameters separately, we proposed the Joint Parameter Estimation method (JPE). In this method, we integrated multiple parameters in the Jaffe–McGramery model into one joint parameter (JP) through a special mathematical transform, which allowed for physical reconstruction based on the joint parameter (JP). Our experimental results show that WaterFormer can effectively restore the color and texture details of underwater images in various underwater scenes with stable performance.

Astrochronology and carbon-isotope stratigraphy of the Fengcheng Formation, Junggar Basin: Terrestrial evidence for the Carboniferous-Permian Boundary - Renda Huang; Fujie Jiang; Di Chen; Ruoyuan Qiu; Tao Hu; Linhao Fang; Meiling Hu; Guanyun Wu; Chenxi Zhang; Jiahao Lv; Yuping Wu; Liliang Huang (Gondwana Research, 2023)

The infertile individual analysis based on whole-exome sequencing in chinese multi-ethnic groups - Qiongzhen Zhao; Yanqi Li; Qi Liang; Jie Zhao; Kai Kang; Meiling Hou; Xin Zhang; Renqian Du; Lingyin Kong; Bo Liang; Weidong Huang (Genes & Genomics, 2023)

Pharmacokinetics and residue elimination of metalaxyl enantiomers in snakehead (Channa argus) - Hao Zhou; Meiyu Zhang; Qi Shan; Heqing Huang; Meiling Zhang; Shugui Liu; Jiawei Lin; Lisha Ma; Guangming Zheng; Lichun Li; Cheng Zhao; Xiaoxin Dai; et al. (Aquaculture, 2023)

Co-pyrolysis of heavy bio-oil and disposable masks pyrolysate with Ce/Fe-based oxygen carrier catalyst - Meiling Yang; Rongyang Zhao; Jianguang Qin; Jinyu Zhang; Laishun Yang; Cuiping Wang; Guangxi Yue (Fuel, 2023)

Negatively regulation of MAVS-mediated antiviral innate immune response by E3 ligase RNF5 in black carp - Jun Yan; Guoxia Qiao; Enhui Wang; Yuqing Peng; Jiamin Yu; Hui Wu; Meiling Liu; Jiagang Tu; Yongan Zhang; Hao Feng (Fish & Shellfish Immunology, 2023)

Self-intercepting interference of hydrogen-bond induced flexible hybrid film to facilitate lithium extraction - Meiling Wang; Tianyuan Zhang; Zhixiang Meng; Chongji Wang; Weikang Dong; Jijian Liu; Su Yang; Xudong Hou; Xiaoran Cheng; Weifeng Liu; Chenyang Xing; Xuguang Liu; et al. (Chemical Engineering Journal, 2023)

Cellulose-based fluorescent materials fabricated in CO2 switchable solvent for freshness monitoring - Yi Sun; Wei Zhang; Shan Lu; Wenhua Miao; Meiling Chen; Fei Liu; Haining Na; Jin Zhu (Carbohydrate Polymers, 2023)

Rapamycin ameliorates brain damage and maintains mitochondrial dynamic balance in diabetic rats subjected to middle cerebral artery occlusion - Changchun Hei; Yujia Zhou; Chenyang Zhang; Furong Gao; Meiling Cao; Shilin Yuan; Yixin Qin; P. Andy Li; Xiao Yang (Metabolic Brain Disease, 2023)

Vertical profile of PCDD/Fs in soil and sediment around an abandoned e-waste dismantling site - Xiaotong Su; Yucheng Zhang; Nora F. Y. Tam; Xiaolan Lao; Meiling Zhong; Qihang Wu; Yingheng Fei; Huifang Lei; Zihui Chen; Bixian Mai; Laiguo Chen (Journal of Soils and Sediments, 2023)

Simultaneous determination of 13 paralytic shellfish toxins and tetrodotoxin in marine shellfish by porous graphitic carbon solid-phase extraction and hydrophilic interaction chromatography-tandem mass spectrometry - Peizhen Li; Rongmao Lu; Jie Zhu; Qingqing Ke; Dingnan Wang; Yang Wang; Chen Zhang; Xinyue Lu; Miaolong Zhao; Zhang Wang; Lingling Pan; Meiling Zhang; et al. (Food Additives & Contaminants: Part A, 2023)

Partial substitution of manure reduces nitrous oxide emission with maintained yield in a winter wheat crop - Huizhou Gao; Yajing Xi; Xueping Wu; Xuexia Pei; Guopeng Liang; Ju Bai; Xiaojun Song; Meiling Zhang; Xiaotong Liu; Zixuan Han; Gang Zhao; Shengping Li (Journal of Environmental Management, 2023)

Eco-friendly waterborne superhydrophobic/superoleophilic FEVE composite coating with prolonged mechanochemical and anti-scaling properties - Zhanjian Liu; Lina Ren; Baoshuang Zhang; Jing Jing; Xiguang Zhang; Meiling Li; Yuxin Fu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

A colloidal aqueous electrolyte modulated by oleic acid for durable zinc metal anode - Meiling Wang; Xiaoyu Wu; Di Yang; Hainan Zhao; Li He; Jiaran Su; Xu Zhang; Xiuxiu Yin; Kangning Zhao; Yizhan Wang; Yingjin Wei (Chemical Engineering Journal, 2023)

SnoRNP is essential for thermospermine-mediated development in Arabidopsis thaliana - Xilong Li; Zongyun Yan; Meiling Zhang; Jiayin Wang; Peiyong Xin; Shujing Cheng; Liquan Kou; Xiaoting Zhang; Songlin Wu; Jinfang Chu; Chengqi Yi; Keqiong Ye; et al. (Science China Life Sciences, 2023)

Comprehensive transcriptome analysis unravels the crucial genes during adventitious root development induced by carbon monoxide in Cucumis sativus L. - Fahong Yun; Dengjing Huang; Meiling Zhang; Chunlei Wang; Yuzheng Deng; Rong Gao; Xuemei Hou; Zesheng Liu; Weibiao Liao (Molecular Biology Reports, 2022)

Comparative analysis of microsatellites in coding regions provides insights into the adaptability of the giant panda, polar bear and brown bear - Meiling Cheng; Daxin Xie; Megan Price; Chuang Zhou; Xiuyue Zhang (Genetica, 2022)

Autonomous selfing is altered by pollination in delayed-selfing species Gentianopsis paludosa (Gentianaceae) - Qinzheng Hou; Xiang Zhao; Meiling Duan; Yiping Zhang (Brazilian Journal of Botany, 2022)

Construction of WO3 nanocubes@Loess for rapid photocatalytic degradation of organics in wastewater under sunlight - Hua Yang; Peiyu Cao; Yaping Zhang; Meiling Zhou; Qianqian Wang; Rongmin Wang; Pengfei Song; Yufeng He (Environmental Science and Pollution Research, 2022)

Adaptive biomineralization in two morphotypes of Sternaspidae (Annelida) from the Northern China Seas - Meiling Ge; Jing Mo; Jack Chi-Ho Ip; Yixuan Li; Wenge Shi; Zongling Wang; Xuelei Zhang; Qinzeng Xu (Frontiers in Marine Science, 2022)
Polychaetes are segmented annelid worms that play a key role in biomineralization in modern oceans. However, little is known about the underlying processes and evolutionary mechanisms. The ventro-caudal shield of Sternaspidae is a typical phosphate biomineral in annelids. Here, we investigated two sternaspids from the northern China Seas, Sternaspis chinensis and Sternaspis liui syn. n, which evolved diverse shield characteristics as local adaptation. Genetic distances, phylogenetic analyses of nuclear markers ( 18S and 28S genes), and mitochondrial genomes revealed that the latter is a junior synonym of the former. The integration of elemental composition and the transcriptomic analysis provided insights into phenotypic shield differences. The electron probe microanalysis showed that shields in S. chinensis were more biomineralized (i.e., with higher iron, phosphorus, and calcium contents) than those in S. liui syn. n. Transcriptomes of the body wall around shields determined 17,751 differentially expressed genes (DEGs) in two morphotypes of the synonymous species. Function enrichment analysis of DEGs showed that S. chinensis has an enrichment of the putative biomineralization pathways (i.e., ion transport and calmodulin binding), while S. liui syn. n consumed more energy and produced more proteins (i.e., oxidative phosphorylation and ribosome). DEGs allowed to identify seven shell matrix proteins expressed differentially in the two morphotypes, especially calponin, filamin, chitinase, and protease inhibitor BPTI/kunitz, which might contribute to shield evolutionary plasticity response to their living habitats. Overall, this study 1) revealed an environmental biomineralization adaptation in two polychaete morphotypes of one species by integrating shield chemical composition of shields and transcriptome analyses and 2) provided insights into the molecular mechanisms underlying polychaete biomineralization.

Performance study of energy conversion system for ocean thermal profiler - Yanhu Chen; Bingzhe Chen; Meiling He; Luning Zhang; Qingchao Xia; Canjun Yang (Frontiers in Marine Science, 2022)
With the increasing scarcity of energy in the world, energy has become an important part of restricting the development and application of traditional ocean profilers. The method of converting ocean thermal energy (OTE) into electrical energy through an energy conversion system is a solution. The model establishment and performance analysis of the energy conversion system are the basis of the ocean thermal profiler (OTP) design. The model and performance are affected by the coupling of multiple parameters, especially rotational speed and pressure. In this study, a universal parameterized model for multi-parameter coupling was proposed. System performance analysis based on experiments including load current, speed, mechanical efficiency and total efficiency was presented. After model parameter identification, the error of mechanical efficiency was within 5%; the total efficiency error was less than 12.8%, and the maximum efficiency point error didn’t exceed 2.21%. The results indicated that the parameterized model was satisfactory for the engineering applications and could guide the design of OTP.

Comparative transcriptome analysis of global effect of ddh and lysE deletion on 4-hydroxyisoleucine production in Corynebacterium glutamicum - Rui Chen; Youhe Xiang; Xinping Yu; Meiling Zhang; Feng Shi (Systems Microbiology and Biomanufacturing, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Role of gibberellin and its three GID1 receptors in Jasminum sambac stem elongation and flowering - Hongliang Zhang; Wei Wang; Jinfeng Huang; Yuting Wang; Li Hu; Yuan Yuan; Meiling Lyu; Binghua Wu (Planta, 2022)

Analyzing the micro-pore characteristics of tight oil reservoirs through the implementation of mercury intrusion technique - Meiling Jiang; Yunfeng Zhang; Yang Liu (Arabian Journal of Geosciences, 2021)

Identification and genomic characterization of emerging CRESS DNA viruses in thoroughbred horses in China - Panpan Tong; Meiling Ren; Xinlong Xu; Xiaozhen Song; Lei Zhang; Ling Kuang; Jinxin Xie (Virus Genes, 2021)

Ternary catalyst Mn-Fe-Ce/Al2O3 for the ozonation of phenol pollutant: performance and mechanism - Manning Zhang; Dulin Yin; Jinjin Guo; Huanghe Wu; Meiling Gong; Xiangdong Feng (Environmental Science and Pollution Research, 2021)

First detection and genetic characterization of equid herpesvirus 2, 4, and 5 in China - Jinxin Xie; Panpan Tong; Lei Zhang; Meiling Ren; Xiaozhen Song; Chenyang Jia; Nuerlan Palidan; Li Zhang; Ling Kuang (Archives of Virology, 2021)

Exendin-4 Reversed the PC12 Cell Damage Induced by circRNA CDR1as/miR-671/GSK3β Signaling Pathway - Hui Quan; Qiudan Chen; Kesheng Wang; Qinwan Wang; Meiling Lu; Yue Zhang; Sujing Qiang; Shaobo Xue; Lin Han; Huanhuan Zhu; Qiangyuan Fan; Meiyu Bao; et al. (Journal of Molecular Neuroscience, 2021)

Study of the lower limit of pore throat filling in tight sandstone reservoir of Gaotaizi oil layer in Qijia area - Meiling Jiang; Yunfeng Zhang; Yang Liu (Arabian Journal of Geosciences, 2021)

The Effect of Composting on the Multiple Heavy Metals in the River Sediment Investigated by Multivariate Analysis - Yaoning Chen; Yanrong Chen; Yuanping Li; Yihuan Liu; Daoli Zhang; Yanxin Wu; Hui Li; Fangting Xu; Meiling Li (Water, Air, & Soil Pollution, 2021)

The complete mitochondrial genome of the hybrid grouper Epinephelus moara (♀)×Epinephelus tukula (♂), and phylogenetic analysis in subfamily Epinephelinae - Zhentong Li; Yongsheng Tian; Meiling Cheng; Linna Wang; Jingjing Zhang; Yuping Wu; Zunfang Pang; Wenhui Ma; Jieming Zhai (Acta Oceanologica Sinica, 2020)

The Role of Arachidonic Acid Metabolism in Myocardial Ischemia–Reperfusion Injury - Changjiang Zhang; Meiling He; Lihua Ni; Ke He; Ke Su; Yinzhi Deng; Yuanhong Li; Hao Xia (Cell Biochemistry and Biophysics, 2020)

Viral aetiology and clinical characteristics of acute respiratory tract infections in Shenzhen during epidemic of coronavirus disease 2019 - Dawei Zhang; Yong Jiang; Jianjiang Hua; Qiong Liu; Wujin Wen; Meiling Zhu; Jikun Du; Helu Liu (Infectious Diseases, 2020)

Retraction Note to: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng‑Jin Guo (Histochemistry and Cell Biology, 2020)

Genetic basis of maize ear angle revealed by high-density single nucleotide polymorphism markers in four recombinant inbred line populations - Jingwei Lin; Shoukun Li; Gengyuan Liang; Meiling Liu; Taicheng Jin; Zhengwei Qu; Haoge Li; Shuisen Chen; Cong Li; Ao Zhang; Yanye Ruan; Zhenhai Cui (Euphytica, 2020)

Construction of Inflammatory Directed Polymer Micelles and Its Application in Acute Lung Injury - Jisen Zhang; Meiling Su; Zongning Yin (AAPS PharmSciTech, 2020)

The inhibition of miR-17-5p promotes cortical neuron neurite growth via STAT3/GAP-43 pathway - Liang Zhang; Zhijie Wang; Bo Li; Ziwei Xia; Xin Wang; Yucai Xiu; Zheng Zhang; Chuanjie Chen; Hong Song; Wenhua Li; Mei Yu; Meiling Zhang; et al. (Molecular Biology Reports, 2020)

Malus niedzwetzkyana (Dieck) Langenf transcriptome comparison and phylogenetic analysis with Malus sieversii (Ledeb) Roem - Meiling Yang; Shiyou Che; Yunxiu Zhang; Wenqin Song; Guorong Yan; Weiwei Yu (Genetic Resources and Crop Evolution, 2020)

Discovery and characterization of a stable lipase with preference toward long-chain fatty acids - Meiling Chen; Xiuzhen Gao; Wu Yang; Caili Sun; Junhuan Yang; Huaiyuan Zhang; Yuanda Song (Biotechnology Letters, 2020)

Genetic Structure and Diversity of Glycyrrhiza Populations Based on Transcriptome SSR Markers - Yaling Liu; Yaping Geng; Meiling Song; Pengfei Zhang; Junling Hou; Wenquan Wang (Plant Molecular Biology Reporter, 2019)

Universal stress protein in Malus sieversii confers enhanced drought tolerance - Meiling Yang; Shiyou Che; Yunxiu Zhang; Hongbin Wang; Tao Wei; Guorong Yan; Wenqin Song; Weiwei Yu (Journal of Plant Research, 2019)

Molecular evidence of goose-parvovirus-related abnormal molting in Pekin ducks - Meiling Jin; Chonglun Feng; Xiaoyan Wang; Dabing Zhang (Archives of Virology, 2019)

Genome-wide investigation of microsatellite polymorphism in coding region of the giant panda (Ailuropoda melanoleuca) genome: a resource for study of phenotype diversity and abnormal traits - Meiling Cheng; Jianying Ren; Fujun Shen; Yan Huang; Zhenxin Fan; Megan Price; Bisong Yue; Xiuyue Zhang (Mammal Research, 2019)

The mechanism of hindering occupants’ evacuation from seismic responses of building - Meiling Xiao; Yao Zhang; Haiyan Zhu (Natural Hazards, 2019)

Genetic characterization of a new astrovirus in goslings suffering from gout - Meiling Jin; Xiaoyan Wang; Kang Ning; Ning Liu; Dabing Zhang (Archives of Virology, 2018)

Response of the groundwater system in the Guanzhong Basin (central China) to climate change and human activities - Wenke Wang; Zaiyong Zhang; Lei Duan; Zhoufeng Wang; Yaqian Zhao; Qian Zhang; Meiling Dai; Huizhong Liu; Xiaoyan Zheng; Yibo Sun (Hydrogeology Journal, 2018)

Gut Microbiota and its Modulation for Healthy Farming of Pacific White Shrimp Litopenaeus vannamei - Erchao Li; Chang Xu; Xiaodan Wang; Shifeng Wang; Qun Zhao; Meiling Zhang; Jian G. Qin; Liqiao Chen (Reviews in Fisheries Science & Aquaculture, 2018)

Combination of NAD+ and NADPH Offers Greater Neuroprotection in Ischemic Stroke Models by Relieving Metabolic Stress - Qiao Huang; Meiling Sun; Mei Li; Dingmei Zhang; Feng Han; Jun Chao Wu; Kohji Fukunaga; Zhong Chen; Zheng-Hong Qin (Molecular Neurobiology, 2018)

Resveratrol promotes the embryonic development of vitrified mouse oocytes after in vitro fertilization - Yang Wang; Meiling Zhang; Zi-Jiang Chen; Yanzhi Du (In Vitro Cellular & Developmental Biology - Animal, 2018)

Long noncoding RNAs in the mTOR signaling network: biomarkers and therapeutic targets - Tinglei Huang; Meiling Wang; Bo Huang; Augustus Chang; Feng Liu; Yanjie Zhang; Bin Jiang (Apoptosis, 2018)

Assessment of debris inputs from land into the river in the Three Gorges Reservoir Area, China - Jing Wan; Yonggui Wang; Meiling Cheng; Bernard A. Engel; Wanshun Zhang; Hong Peng (Environmental Science and Pollution Research, 2018)

Characterization of a novel dsRNA mycovirus isolated from strain A105 of Rhizoctonia solani AG-1 IA - Meiling Zhang; Li Zheng; Chen Liu; Canwei Shu; Erxun Zhou (Archives of Virology, 2018)

Multiple timescale analysis of the urban heat island effect based on the Community Land Model: a case study of the city of Xi’an, China - Meiling Gao; Huanfeng Shen; Xujun Han; Huifang Li; Liangpei Zhang (Environmental Monitoring and Assessment, 2018)

Spatial and temporal variability in the net primary production of grassland in China and its relation to climate factors - Meiling Zhang; Rattan Lal; Youyi Zhao; Wenlan Jiang; Quangong Chen (Plant Ecology, 2017)

Development of Fluorescence-Linked Immunosorbent Assay for Icariin - Jinjun Cheng; Yan Zhao; Meiling Zhang; Yue Zhang; Xiaoman Liu; Xin Yan; Yongzhi Wang; Ziwei Sun; Qingguo Wang; Huihua Qu (Journal of Fluorescence, 2017)

A glucuronokinase gene in Arabidopsis, AtGlcAK, is involved in drought tolerance by modulating sugar metabolism - Wenjun Xiao; Shuai Hu; Xiaoxun Zhou; Runyu Yao; Jingru Luo; Congying Yuan; Hongping Chang; Cheng Zhang; Ji Huang; Jinyan Li; Shucan Liu; Meiling Li; et al. (Plant Molecular Biology Reporter, 2017)

Allelism analysis of BrRfp locus in different restorer lines and map-based cloning of a fertility restorer gene, BrRfp1, for pol CMS in Chinese cabbage (Brassica rapa L.) - Huamin Zhang; Junqing Wu; Zihui Dai; Meiling Qin; Lingyu Hao; Yanjing Ren; Qingfei Li; Lugang Zhang (Theoretical and Applied Genetics, 2017)

Accumulation of intact sulfur mustard in adipose tissue and toxicokinetics by chemical conversion and isotope-dilution liquid chromatography–tandem mass spectrometry - Bin Xu; Cheng Zong; Yajiao Zhang; Tianhong Zhang; Xiaoying Wang; Meiling Qi; Jianfeng Wu; Lei Guo; Peng Wang; Jia Chen; Qin Liu; Hua Xu; et al. (Archives of Toxicology, 2017)

Abnormal Functional Connectivity Density in Post-traumatic Stress Disorder - Youxue Zhang; Bing Xie; Heng Chen; Meiling Li; Feng Liu; Huafu Chen (Brain Topography, 2016)

Integrating Genome-Wide Association Study and Brain Expression Data Highlights Cell Adhesion Molecules and Purine Metabolism in Alzheimer’s Disease - Zimin Xiang; Meiling Xu; Mingzhi Liao; Yongshuai Jiang; Qinghua Jiang; Rennan Feng; Liangcai Zhang; Guoda Ma; Guangyu Wang; Zugen Chen; Bin Zhao; Tiansheng Sun; et al. (Molecular Neurobiology, 2015)

Two distinct classes of protein related to GTB and RRM are critical in the sclerotial metamorphosis process of Rhizoctonia solani AG-1 IA - Canwei Shu; Jieling Chen; Si Sun; Meiling Zhang; Chenjiaozi Wang; Erxun Zhou (Functional & Integrative Genomics, 2015)

A numerical study of the generation mechanism of internal solitary waves in the Luzon Strait - Jing Wang; Meiling Sun; Xudong Zhang; Lina Sun; Junmin Meng (Acta Oceanologica Sinica, 2015)

Photoperiod and shading regulate coloration and anthocyanin accumulation in the leaves of malus crabapples - Yanfen Lu; Meiling Zhang; Xiaona Meng; Huihua Wan; Jie Zhang; Ji Tian; Suxiao Hao; Kaina Jin; Yuncong Yao (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Characterization of Post-traumatic Stress Disorder Using Resting-State fMRI with a Multi-level Parametric Classification Approach - Feng Liu; Bing Xie; Yifeng Wang; Wenbin Guo; Jean-Paul Fouche; Zhiliang Long; Wenqin Wang; Heng Chen; Meiling Li; Xujun Duan; Jiang Zhang; Mingguo Qiu; et al. (Brain Topography, 2015)

RETRACTED ARTICLE: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng-Jin Guo (Histochemistry and Cell Biology, 2014)

Amyloid Beta-Derived Diffusible Ligands (ADDLs) Induce Abnormal Expression of Insulin Receptors in Rat Hippocampal Neurons - Xin Liu; Zongyan Teng; Can Cui; Ruitao Wang; Meiling Liu; Yina Zhang (Journal of Molecular Neuroscience, 2014)

The complete genomic sequence of a novel mycovirus from Rhizoctonia solani AG-1 IA strain B275 - Li Zheng; Huiquan Liu; Meiling Zhang; Xiong Cao; Erxun Zhou (Archives of Virology, 2013)

Resveratrol protects against arsenic trioxide-induced nephrotoxicity by facilitating arsenic metabolism and decreasing oxidative stress - Meiling Yu; Jiangdong Xue; Yijing Li; Weiqian Zhang; Dexing Ma; Lian Liu; Zhigang Zhang (Archives of Toxicology, 2013)

Analysis of ΔpH and the xanthophyll cycle in NPQ of the Antarctic sea ice alga Chlamydomonas sp. ICE-L - Shanli Mou; Xiaowen Zhang; Naihao Ye; Jinlai Miao; Shaona Cao; Dong Xu; Xiao Fan; Meiling An (Extremophiles, 2013)

In vitro evaluation of a mammary gland specific expression vector encoding recombinant human lysozyme for development of transgenic dairy goat embryos - Tao Gui; Meiling Zhang; Jianwen Chen; Yuanliang Zhang; Naru Zhou; Yu Zhang; Jia Tao; Liucai Sui; Yunsheng Li; Ya Liu; Xiaorong Zhang; Yunhai Zhang (Biotechnology Letters, 2012)

Structure and seasonal dynamics of bacterial communities in three urban rivers in China - Meiling Zhang; Na Yu; Liqiao Chen; Caihong Jiang; Yanjie Tao; Tian Zhang; Jun Chen; Di Xue (Aquatic Sciences, 2012)

Mining EST-Derived SSR Markers to Assess Genetic Diversity in Cassava (Manihot esculenta Crantz) - Meiling Zou; Zhiqiang Xia; Peng Ling; Yang Zhang; Xin Chen; Zusheng Wei; Weiping Bo; Wenquan Wang (Plant Molecular Biology Reporter, 2011)

Characterization and identification of Sox2+ radial glia cells derived from rat embryonic cerebral cortex - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Jinhong Shi; Weiwei Yang; Xuefeng Tan; Xinhua Zhang; Linqing Zou (Histochemistry and Cell Biology, 2011)

Molecular characterization of the bacterial composition in two waste silk refining systems - Meiling Zhang; Xuexia Yang; Tian Zhang; Jun Chen; Di Xue (World Journal of Microbiology and Biotechnology, 2011)

Effect of trichostatin A and 5-Aza-2′-deoxycytidine on transgene reactivation and epigenetic modification in transgenic pig fibroblast cells - Qingran Kong; Meiling Wu; Zhenkun Wang; Xinmiao Zhang; Lu Li; Xiangyu Liu; Yanshuang Mu; Zhonghua Liu (Molecular and Cellular Biochemistry, 2011)

Generation and identification of rat fetal cerebral radial glia-like cells in vitro - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Xuefeng Tan; Xinhua Zhang; Weiwei Yang; Jinhong Shi; Linqing Zou (In Vitro Cellular & Developmental Biology - Animal, 2011)

Transcriptional analysis of the titin cap gene - Shuang Zhang; Priya Londhe; Meiling Zhang; Judith K. Davie (Molecular Genetics and Genomics, 2011)

Long-term cultured callus and the effect factor of high-frequency plantlet regeneration and somatic embryogenesis maintenance in Zoysia japonica - Li Liu; Xiaoli Fan; Junwei Zhang; Meiling Yan; Manzhu Bao (In Vitro Cellular & Developmental Biology - Plant, 2009)

Role and relationship of nitric oxide and hydrogen peroxide in adventitious root development of marigold - Weibiao Liao; Honglang Xiao; Meiling Zhang (Acta Physiologiae Plantarum, 2009)